Harnessing a marine-derived Rhodococcus strain for cross-habitat bioaugmentation of malodorant skatole: Performance and ecological response - Genxiu Li; Nan Meng; Jiaxin Zhang; Jiahui Liu; Wen Kuang; Jia Shi; Chao Chen; Jicheng Yu; Qiu Liu; Qiao Ma (Marine Pollution Bulletin, 2026)

Integrating genomic distance analyses in the description of a new family, genus, and species of sponge-associated antipatharians (black corals) - Erika Gress; Yi-Xuan Li; Dennis M. Opresko; Jian-Wen Qiu (Molecular Phylogenetics and Evolution, 2026)

Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Self-supporting, binder-free NiCoAl-LTH/NF composite electrodes for high-efficiency membrane-free capacitive deionization - Ya-Qi Jiang; Yun-Ze Qiu; Chun-Miao Zhang; Qin Li; Jing-Jing Feng; Wen-Qing Fei; Xue-Fei Sun (Desalination, 2026)

Signal molecules in microalgal-bacterial partial nitrification-anammox systems: Roles, mechanisms, and prospects - Qian Bi; Shuang Qiu; Wen Tang; Mengting Li; Zhenyu Kong; Yanbing Hu; Zhipeng Chen; Xiang Li; Ayesha Algade Amadu; Shijian Ge (Water Research, 2026)

CaMYB30 positively activate the expression of CaWRKY29 and regulates salt stress via modulating ROS homeostasis in pepper (Capsicum annuum L.) - Liping Qiu; Huibin Han; Yue Wang; Yongkang Hu; Lu Zhang; Hui Li; Yufang Wen; Yun Yu; Chao Ji; Jianping Liu (Plant Science, 2026)

Intermittent stirring-mediated solids retention time–hydraulic retention time decoupling enhances side-stream enhanced biological phosphorus removal performance and microbial selection - Yanzhe Gong; Dongqi Wang; Wengui Gu; Ruoyu Wu; Guangxiang Duan; Jiayu Bi; Xiaopeng Qiu; Yuan Guo; Yishan Lin; Hongfang Sun; Xi Wen; Chenxin Tang; et al. (Journal of Environmental Chemical Engineering, 2026)

Ganoderma lucidum ethanol extract attenuates depressive-like behaviors and is associated with modulation of NF-κB/NLRP3-related neuroinflammation and BDNF/TrkB signaling - Yiwei Zheng; Xiao Chen; Liujing Li; Jiangfeng Wen; Ruijuan Qiu; Hao Ma; Chunlin Chen (Food Bioscience, 2026)

Exploring hemopexin's antibacterial activity in bony fish: An immunological study of PoHpx-a - Sheng-han Gao; Yi-qi zhou; Wen Du; Qiu Jin; Fei Wang; Xue-peng Li (Fish & Shellfish Immunology, 2026)

Green manuring promotes grain yield and nitrogen use efficiency of spring wheat under chemical nitrogen reduction by enhancing plant nitrogen uptake and soil nitrogen supply - Yanwei Guo; Wen Yin; Hailong Qiu; Pan Li; Jingui Wei; Diankai Zhang; Lianhao Zhao; Pingxing Wan; Zhilong Fan; Falong Hu; Yunyou Nan; Qiang Chai; et al. (Field Crops Research, 2026)

Enhancing photosynthetic traits and source-sink relationships through organic fertilizer substitution to improve maize radiation use efficiency and yield stability under reduced irrigation - Feier Wang; Pan Li; Hailong Qiu; Xinyuan Ma; Jing Zhu; Lianhao Zhao; Pingxing Wan; Zhilong Fan; Falong Hu; Qiang Chai; Heyu Chen; Mohamed Abdalla; et al. (Field Crops Research, 2026)

Metal Bi-coupled chiral nanoscale structures enhance spin-polarized electrons to promote photocatalytic CO2 reduction - Dan Wu; Yanni Lang; Liang Xu; Qiyuexin Wang; Qiu Fu; Bingli Li; Xinye Zhao; Zhaoyi Yin; Yongjin Li; Dacheng Zhou; Yangke Cun; Zhiguo Song; et al. (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

A tea exosome-integrated self‑oxygenating cascade chitosan/oxidized alginate hydrogel for remodeling the hyperglycemic and hypoxic microenvironment in diabetic wound healing - Li-Hua Xie; Xin-Hui Zhou; Wei-Qiu Wen; Wei Wang; Ping Gui; Li Li; Guan-Hai Wang (Carbohydrate Polymers, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Theoretical and numerical study on discontinuous Galerkin flux reconstruction method in thermal-hydraulic analysis - Wen Zhibo; Li Xinyu; Zhang Dalin; Qiao Pengrui; Tian Wenxi; Qiu Suizheng; Su Guanghui (Annals of Nuclear Energy, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

Source-dependent of dissolved organic matter interfacial transport and component fractionation retention in NAPL-contaminated aquifers - Peng Wang; Shangyan Li; Yue Qiu; Yuanjie Guo; Wen Zhang; Shengyan Pu (Water Research, 2026)

Genome-wide identification of Nitrate Transporter 1/Peptide Transporter Family (NPF) genes in pear (Pyrus bretschneideri) and functional characterization of PbNPF5.7 in fire blight - Lun Li; Chenyang Chen; Keliang Fu; Nie Feng; Taotao Qiu; Yueqi Xu; Qionghou Li; Xin Yan; Jia Tian; Yue Wen; Shaoling Zhang; Xiaosan Huang (Plant Science, 2026)

Fluorescence and SERS dual-mode sandwich lateral flow test strip utilizing concanavalin A modified trimetallic polydopamine with rhodamine B loaded UiO-66 immunoprobe for visual and sensitive detection of Escherichia coli - Wen-Bo Zhao; Xiao Liang; Zi-Tao Zhong; Liu Yuan; Ji-Tao Li; Qiu-Lan Li; Qin-Qin Han; Ya-Ling Yang (Food Bioscience, 2026)

TBK1 associates with TRIF and TRAF3 related IRF3, IRF7, and type I IFN signaling in large yellow croaker Larimichthys crocea - Ying Li; Wen Qi Zha; Wen Feng Cui; Meng Jia Li; Yan Mi Na Chen; Qiu Ye Huang; Qiao Yun Yang; Ying Jia Shen; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Fabrication of a fluorescence/colorimetric multi-channel sensor array utilizing riboflavin derived bimetallic-doped Ce-MOF based peroxidase mimic for highly efficient determination of heavy metal ions - Xiao Liang; Qiu-Lan Li; Wen-Bo Zhao; Peng Yang; Ya-Ling Yang; Zi-Tao Zhong (Environmental Research, 2026)

Injectable photo-crosslinkable GelMA hydrogel incorporating quercetin@Zif-8 nanocarriers for osteoimmunomodulation and bone regeneration - Qing Gao; Wanshuang Zhang; Yi Li; Li Lin; Wen Jin; Jiayin Qiu; Kai Xie; Xianfa Yuan (Chemical Engineering Journal, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Antibacterial activity and mechanism of mangosteen extract garcinone D against Bacillus cereus - Ya-Ya Lei; Guan-Qiu Zhou; Yu-Chen Sun; Jin-Cheng Ma; Fu-Li Liu; Bao-Qi Zhang; Wen Zhang; Li-jing Zhang; Yan-Ze Wang; Ying-Qian Liu (International Journal of Food Microbiology, 2026)

Two-step pyrolysis enabled by bentonite catalysis for the co-production of bioactive humic acid and functional carbon-clay composites - Huanhuan Li; Jiarun Duan; Lijuan Zhang; Yong Wen; Yun Xiang; Chen Qiu; Junmei An; Zhiguo Guo; Yidong Cai; Changchun Ge; Xiaona Ren; Xinjiang Zhou; et al. (Environmental Research, 2026)

Discrete element investigation of particle breakage and macro–micro behaviour of rockfill materials under flexible boundary triaxial compression - Weifeng Cao; Yanlong Li; Zheng Si; Lifeng Wen; Peng Bu; Wen Qiu; Weibo Zhao (Computers and Geotechnics, 2026)

Regulating the inverse modes of Jahn-Teller distortions at cobalt and iron sites for enhanced oxygen evolution reaction - Fanghua Liu; Chizhong Wang; Wen Guo; Kaiyang Pan; Lei Qiu; Xiaolin Ma; Sizhe Chen; Jiawei Li; Junhua Li; Huazhen Chang (Chemical Engineering Journal, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Chemical constituents from the roots of Illigera celebica - Si-Feng Yang; Lin-Wen Yi; Qiu-Xia Huang; Xing-Meng Luo; Xiao-Bing Su; Lin Hu; Wen-Ting Li; Xiang-Zhong Huang; Meng-Yuan Jiang (Natural Product Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Inhibitory effect of moisture loss on braised pork quality by rapid cooling assisted with static magnetic field - Lirong Jia; Haijun Qiao; Hong Zhu; Pengcheng Wen; Zhilong Jia; Pengjie Wang; Xingmin Li; Ju Qiu (Meat Science, 2026)

Life cycle assessment of regionally functionally-zoned intensive pig farming systems: Carbon footprint analysis and mitigation strategies for sustainable production - Bing Wu; Zhiqi Wen; Zhepu Ruan; Xiaoxuan Lin; Yongjie Li; Zhuobiao Ni; Gengyuan Cai; Rongliang Qiu (Journal of Environmental Management, 2026)

Direct visual evidence of S-scheme charge transfer: CeO2 quantum dots anchored on CdS nanosheets for synergistically enhanced photocatalysis - Yaodi Fu; Ke Wen; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Environmental Research, 2026)

High-efficiency integration of capacitive deionization and electricity generation in single cycle enabled by basswood-derived free-standing carbon electrode - Yao Qiu; Rui Zhang; Shuyu Kong; Yishuo Teng; Dongling Li; Ming Hou; Jingwen Wang; Yongzhao Hou; Guangwu Wen; Dong Wang (Desalination, 2026)

Overtopping Breach of Cascade Earth-Rock Dams – State of the Art Review - Wen Qiu; Yanlong Li; Lifeng Wen; Ye Zhang; Ting Wang; Qiang Zhang; Haotian Chen (Water Resources Management, 2026)

Unveiling the structural determinants of PFASs acute inhalation toxicity: an integrated approach using QSAR, q-RASAR, and interspecies extrapolation - Manyi Qiu; Jieyi Yang; Ying’ai Pang; Yunman Wen; Le Yang; Guoliang Li; Qiaoyuan Yang; Lili Liu (Archives of Toxicology, 2026)

REE source, fractionation and enrichment behavior in the Tuguanzhai-Maliping ion-adsorption REE deposit, Tengchong Block (SW China) - Zhong Tang; Congfa Bao; Tianxue Ming; Hanjie Wen; Xiaohu He; Hao Cheng; Jiaxin Liu; Zewei Pan; Liang Li; Jiasheng Wang; BeiBei Chen; Kunfeng Qiu (Acta Geochimica, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Efficacy and mechanisms of hydrosedimentary regulation in a typical loess plateau watershed under different governance stages - Hunan Qiu; Peng Li; Wen Wang; Honglei Tang; Shengde Yu; Shu Yu (CATENA, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Thyroid hormone potentiates androgen-induced sex reversal during early gonadal differentiation in orange-spotted grouper, Epinephelus coioides - Liyuan Luo; Chuan Chen; Qian Xiao; Wen Li; Xinyi Li; Lixi Qiu; Chongqing Qu; Jinhui Wu; Jingxiong Huang; Qing Wang; Huihong Zhao (Aquaculture, 2026)

Enhancing emulsion stability and whipping properties in recombined creams: Glycosylated casein conjugates for clean-label applications - Hongjuan Li; Kuan Liang; Juan Zhang; Feiyang Liu; Xin Wen; Aijia Han; Yaqi Qiu; Yongqiang Cao; Hongbo Li; Jinghua Yu (Food Hydrocolloids, 2026)

Converting low-quality construction waste into tough pavement material via biomimetic mineralization - Long Wen; Zhi Zhao; Yang Li; Yiran Wang; Jiaran Han; Chuan Qiu; Hui Yao; Runhua Guo; Kai Li; Xiaoyan Song (Chemical Engineering Journal, 2026)

Seneciphylline induces hepatotoxicity through mitochondrial apoptosis: mechanistic elucidation and in vitro-to-in vivo prediction via physiologically based pharmacokinetic modeling-facilitated reverse dosimetry - Yu-Shun Lu; Jiang Ma; Yuan Geng; Bing-Yan Zhang; Zheng Ding; Xiao-Li Shi; Yan-Yang Xu; Jing Qiu; Yong-Zhong Qian; Wen-Biao Shi; Lu Chen (Chemico-Biological Interactions, 2026)

Impact of air pollution control strategies on full-phase chlorine species emissions from coal-fired power plants in China during 2013-2022 - Yuying Tang; Yulong Yan; Xionghui Qiu; Zhijian Li; Manli Wang; Zhen Li; Minneng Wen; Wenyi Jin; Yuyang Cheng; Lin Peng (Atmospheric Environment, 2026)

An AcMYB10-AcF3GT1/GST1 module restricts anthocyanin synthesis in the fruit flesh of kiwifruit - Xiao-tian Li; Zhi-xia Huang; Yu-xiao Zhai; Ya-ting Guo; Yi-tong Liu; Yan Zhang; Zhu Xie; Andrew C. Allan; Xue-ren Yin; Wen-qiu Wang (Plant Cell Reports, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Poly(o-phenylenediamine) nanosheets-based dual-mode fluorescence probe for ultrasensitive detection of perfluoroalkyls in water environment - Yanhua Zhang; Wen Yao; Jian Guo; Hongyuan Huang; Jie Yang; Jiahuang Qiu; Tianxin Li; Yubo Wei; Xinrong Guo (Analytica Chimica Acta, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

Competitive nitrogen/phosphorus scarcity triggers multi-pathway nitrogen removal and phosphorus-stress response in microalgae-bacterial symbiosis: poly-metabolic synergy enhancement mechanisms - Lili Yang; Wenqian Wei; Xin Sun; Xiang Li; Xiaowen Wen; Binchen Mao; Ran Hao; Weihan Qiu; Huipeng Li (Bioresource Technology, 2026)

Unveiling a macrophage-driven inflammatory dysregulation: NF-κB-mediated hyperinflammation links 6PPD-Q exposure to viral immunopathology - Xia-Wen Qiu; Jiajun Chen; Jiayan Wang; Yujie Li; Xiaoyan Qi; Xianchang Zeng; Huajun Feng; Xianghui Kong (Journal of Hazardous Materials, 2026)

County-level emission inventory reveals substantial contributions of small and medium-sized cities to air pollutants and CO2 emissions in China - Zhezhe Shi; Shengyue Li; Qingru Wu; Kaiyun Liu; Yuying Cui; Daiwei Ouyang; Xiaoming Gu; Jia Liu; Xionghui Qiu; Zeqi Li; Hao Wang; Yanning Zhang; et al. (Journal of Environmental Management, 2026)

The moon's formation time recorded in lunar mare basalts - Mu-Han Yang; Qian W.L. Zhang; Richard W. Carlson; Bi-Wen Wang; Dongjian Ouyang; Qiu-Li Li (Icarus, 2026)

Microwave-assisted extraction enhances the epicatechin and bovine serum albumin the interaction by inducing protein conformational changes - Wen-Ting Duan; Jiang-Feng Yuan; Li-Juan Wang; Meng-Xue Sun; Xiao-Wen Yang; Zhi-Jun Qiu (Food Chemistry, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Effect of permethrin insecticide on TRβ-mediated cone photoreceptor differentiation and spectral sensitivity in zebrafish larvae (Danio rerio) - Shiyong Wen; Liguo Qiu; Cuiping Wen; Xuechu Du; Xunfan Wei; Liying Xiao; Xiuli Sun; Wen Li; Wenjiao Li; Peng Yu; Panpan Zhu; Jing Tao (Environmental Research, 2026)

Multifunctional pomelo peel cellulose/lysine/ZIF-8 porous foam with honeycomb structure: Adsorption performance and mechanism - Haize Su; Weipeng Qiu; Tenggen Hu; Shaohua Luo; Jinling Wu; Xiaowen Zhong; Na Li; Hao Su; Zhizhou Ling; Zhenlin Xu; Hong Wang; Peng Wen (Carbohydrate Polymers, 2026)

ALS2, encoding a plastid 50 S ribosomal protein L5, is essential for early chloroplast development in rice - Zhennan Qiu; Chunmiao Wang; Wenjiao Li; Zhenwu Guan; Peiliang Zhang; Peinan Sun; Liying Xiao; Shiyong Wen (Journal of Plant Research, 2026)

The histone demethylase KDM4A promotes esophageal cancer progression by epigenetically activating LRG1-mediated TGF-β signaling - Yueting Han; Huiya Wang; Yaoyang Guo; Hongdian Zhang; Xinyi Wen; Miao Zhang; Zhanhua Gao; Jie Hao; Minghan Qiu; Li Ren; Dongzhi Hu; Yi Ba; et al. (Apoptosis, 2026)

Thermochromic hydrogels for thermal management smart windows - Mukun Li; Peiyu Qiu; Haobo Wen; Kunpeng Ruan; Junwei Gu (Science Bulletin, 2026)

Single-cell omics analysis reveals tumor microenvironment rewiring after arsenic trioxide therapy in acute promyelocytic leukemia - Gang Xu; Jiyu Guo; Shengjin Fan; Si Li; Ting Qiu; Zefeng Chen; Yanan Liu; Luan Wen; Chongwen Lv; Yanan Jiang; Huitao Fan; Juan Xu; et al. (Science Bulletin, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Bisphenol exposure during pregnancy and serum total bile acid levels across trimesters: single and combined effects in pregnant women from Guangxi Zhuang, China - Jun Liang; Yu Zou; Zican Mo; Lixiang Pang; Kaiqi Yang; Peng Tang; Qian Liao; Liujuan Ou; Junshang Wen; Wanhui Li; Huishen Huang; Xiaoqiang Qiu (Environmental Pollution, 2026)

Tailored plasmonic interfaces on LAS glass-ceramic gratings for high-efficiency electromagnetic wave absorption - Chunyan Ding; Shanshan Fan; Zhengliang Qiu; Zhuoyang Li; Yiteng Zhang; Songsong Wu; Liping Tong; Bo Zhong; Long Xia; Guangwu Wen; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

CaWRKY6-CaERF3 regulate ROS homeostasis to positively modulate salt stress in pepper (Capsicum annuum L.) - Zhimin Li; Huibin Han; Hui Li; Zhen An; Yue Wang; Yufang Wen; Liping Qiu; Chao Ji; Qinghong Zhou; Jianping Liu (Plant Cell Reports, 2026)

Cytochalasans from the fungus Chaetomium globosum with cytotoxic activities against HepG2 cell line - Hong-Fei Li; Tian Jin; Jiao-Xian Du; Xin-Wen Luo; Guo Zhang; Wang-Qiu Deng; Juan He; Tao Feng (Phytochemistry, 2026)

Effects of different drying methods on the physicochemical properties, antioxidant activity and gut microbiota fermentation behaviours of polysaccharides from Schizophyllum commune - Lihong Fan; Chaomin Yin; Haina Ma; Jing Wen; Maofen Yi; Zhenshun Li; Xiuzhi Fan; Defang Shi; Zhicheng Huang; Jianhui Qiu; Hong Gao (Food Research International, 2026)

Comparison of physicochemical properties of water- and alkaline-extracted polysaccharides from Schizophyllum commune and their anti-obesogenic effects in vivo - Chen Li; Chaomin Yin; Jiangtao Li; Jing Wen; Lihong Fan; Haina Ma; Xiuzhi Fan; Defang Shi; Wei Yu; Jianhui Qiu; Hong Gao (Food Chemistry, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Depth-dependent effects of vegetation restoration on soil quality in ion-adsorbed rare earth leach residues: Insights from soil functions - Heng Zhang; Xianzhen Luo; Rui Zhang; Li Zhou; Rufeng Guo; Yuanwen Kuang; Dazhi Wen; Biao Qiu; Lingling Zhang (CATENA, 2026)

Simultaneous and efficient removal of carbon, nitrogen, and phosphorus by Pseudomonas mendocina MGAD-04 under aerobic conditions: Performance and mechanism - Qiu-Gang Wang; Wei-Yi Shi; Ke-Jia Zhang; Pu Wang; Wen-Huai Wang; Jun-Feng Li (Bioresource Technology, 2026)

Effect of thermal alkaline and thermal hydrolysis on the methane production and antibiotic resistance genes removal during sewage sludge anaerobic digestion - Ruoxin Li; Chunsheng Qiu; Nannan Liu; Wen Zhang; Xu Chen; Yaping Zhang; Chenchen Wang; Shaopo Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Pharmacological Inhibition of JAK/STAT-IL2 Axis Alleviated Cisplatin-Induced Ototoxicity - Shimei Zheng; Chang Liu; Jiahuan Li; Hongbo Yu; Siyu Qiu; Wen Li; Liping Zhao; Xiangli Zeng; Bing Chen; Yingzi He (Molecular Neurobiology, 2026)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

Structure-optical activity relationship of chiral helical gold nanorods and their application in alkaline phosphatase detection - Shuai Wen; He Feng Shi; Can Nan Zhao; Ying Ying Xiong; Liang Tong Li; Qiu Yue Liu; Chen Liu; Qiu Sha Li; Wei Wang; Jian Wang (Chemical Engineering Journal, 2025)

Amino-directed shifting ethylene/acetylene/ethane separation in pore-space-partitioned metal-organic frameworks - Li-Qiu Yang; Yan-Fei Li; Jia-Yao Liu; Ying Wang; Wen-Yu Yuan; Quan-Guo Zhai (Chemical Engineering Journal, 2025)

Phenolics from Toxicodendron vernicifluum (Stokes) F. A. Barkley (Anacardiaceae) and their chemotaxonomic significance - Cai-Wen Meng; Wen-Jing Zu; Jie Liu; Xue Qiu; Hong-Yun Bai; Jian-Yu Liu; Yong-Nan Xu; Mei-Chen Li (Biochemical Systematics and Ecology, 2025)

A novel cucurbit[8]uril-based fluorescent probe for the detection of phenethylamine in urine - Min Chen; Wen Min; Shang-Wei Yuan; Carl Redshaw; Li-Xia Chen; Qiu-Yu Peng; Tao Yang; Zhu Tao; Xin Xiao (Analytica Chimica Acta, 2025)

Gut microbiota modulation by structurally diverse foodborne polysaccharides: In vitro fermentation and prebiotic activity evaluation - Lu Wang; Jia-hao Fan; Yao Yang; Hong-wei Qiu; He-he Li; Wen-yi Kang; Guang-ping Lv (Food Bioscience, 2025)

Enhanced effects of species richness on cadmium phytoextraction across eastern China: A meta-analysis - Rufeng Guo; Xianzhen Luo; Li Zhou; Rui Zhang; Lingling Zhang; Yuanwen Kuang; Biao Qiu; Dazhi Wen (Environmental Research, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

Eco-friendly taro stem-sourced cellulose/polypyrrole hybrid aerogel: An efficient capture strategy for microplastics removal - Wei-peng Qiu; Hai-ze Su; Hao Su; Shao-hua Luo; Li-shan Lai; Jia-le Zhu; Zhen-lin Xu; Hong Wang; Peng Wen (Chemical Engineering Journal, 2025)

A new AgTe0.08S1.67 QDs-based fluorescence sensing platform for rapidly detect UO22+ in water environment - Huan Yang; Danyan Lin; Jie Yang; Jiahuang Qiu; Juxiao Li; Tianxin Li; Yubo Wei; Wen Yao; Xinrong Guo (Analytica Chimica Acta, 2025)

Environmental nano-particulates induced pre-implantation embryonic toxicity in pluripotent stem cell-derived blastoids - Gaojing Liu; Yayuan Li; Xiuyun Liu; Wei Wang; Xiao Wen; Yange Che; Qiu Tu; Bo Zhao (Environmental Pollution, 2025)

High-efficiency enrichment process of uranium from amidoxime-functionalized fibers after treated by alkaline elution system - Shen Zhang; Wencai Cheng; Congcong Ding; Ze Qiu; Junwen Tan; Xirui Lu; Jun Wen; Hao Li (Chemical Engineering Journal, 2025)

Resolving the Genetic Divergence and Population Structure in the Circumpolar Ophiuroid Ophiura sarsii Complex - Yi‐Xuan Li; Sophia Nazarova; Jack Chi‐Ho Ip; Evgeny Genelt‐Yanovskiy; Ting Xu; Yue Dong; Jian‐Wen Qiu; Xue‐Lei Zhang; Qin‐Zeng Xu (Journal of Biogeography, 2025)
Aim The presence of cryptic species causes significant challenges to biodiversity assessment and biological resources management. Here, we investigate the genetic structure and biogeographical patterns of a complex ophiuroid species as a case study. Location Yellow Sea and Funka Bay in the Western Pacific Ocean, Bering Sea in the Arctic Ocean and Barents Sea in the Atlantic Ocean. Taxon The circumpolar ophiuroid Ophiura sarsi i , a common benthic species across the Arctic seas, has at least two cryptic lineages. Methods To better understand the genetic structures and the underlying evolutionary processes in the O. sarsii species complex, we compared the genome‐wide single nucleotide polymorphism (SNP) data and COI of five geographical populations across the northern Pacific, Arctic and Atlantic Oceans using the 2b‐RAD sequencing approach. Results Results clearly showed three highly diverged evolutionary lineages: northern Pacific lineage ( O. sarsii vadicola ), Pacific‐Arctic lineage ( L A ) and Atlantic lineage ( L B ). The divMigrate analysis revealed significant gene flow within O. sarsii vadicola populations and O. sarsii L A populations, but no cross‐species gene flow. Demographic analysis was used to estimate their historical divergence, in which the differentiation of O. sarsii vadicola predated that of the other two lineages of O. sarsii . Molecular dating resulted in an estimation of their divergence events between 3.88 and 1.67 Ma at Pliocene–Pleistocene using COI . Functional analysis revealed several enriched signalling pathways, potentially involved in ophiuroids' environmental adaptation. Main Conclusions Our study suggests three lineages of the cryptic species O. sarsii could split into at least two genetic species, including O. sarsii vadicola , North Pacific–Arctic and Atlantic O. sarsii . The hidden evolutionary trajectory is uncovered for the O. sarsii complex, shaped by paleoclimate and ocean currents. We emphasise the need for genome‐wide SNP applications to understand the ophiuroid biodiversity and contribute to conservation in the Pacific–Arctic region.

Transcriptional factors AcNAC1/2 synergistically orchestrate kiwifruit chlorophyll degradation - Ying-ying Wu; Shi Wu; Xin-yi Li; Jia-hui Deng; Pu Liu; Wen-qiu Wang; Xue-ren Yin; Xiao-fen Liu (Postharvest Biology and Technology, 2025)

Urinary monohydroxylated polycyclic aromatic hydrocarbons among healthy elderly in the China BAPE study: Exposure characteristics, influencing factors, and health risks - Jiankun Qian; Xiaojie Guo; Chenglei Qi; Peijie Sun; Chenfeng Li; Chenlong Li; Kangning Cao; Yibo Xu; Huimin Ren; Jiran Zhang; Yu Wang; Shan Bao; et al. (Journal of Hazardous Materials, 2025)

Tracking climate fluctuations in the North China during the Carboniferous-Permian transition using chemical weathering indices - Wanli Gao; Qin Zhang; Jingtao Zhao; Qiang Fang; Wen Liu; Weiliang Kong; Wenyu Li; Hongjie Peng; Tianquan Qu; Guangyin Cai; Jianghai Yang; Zhen Qiu (Global and Planetary Change, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The impact of counter-flow fin-shape rods cylinder and its geometric parameters on wind-induced vibration energy harvester - Jian Qiu; Qiaoya Lv; Hanpei Xu; Dongling Li; Quan Wen (Ocean Engineering, 2025)

Mineralogical and chronological records of strong shock metamorphism in pigeonite cumulate eucrite Northwest Africa 8326 - Lang Zhang; Ai-Cheng Zhang; Xiao-Wen Liu; Yan-Jun Guo; Jia-Ni Chen; Yuan-Yun Wen; Qiu-Li Li; Yu Liu; Xiao-Xiao Ling; Jin S. Zhang (Geochimica et Cosmochimica Acta, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Spatial dynamics of phosphorus mobilization by mycorrhiza - Yi-Wen Liu; Dong-Xing Guan; Li-Xue Qiu; Yu Luo; Fei Liu; H. Henry Teng; Yakov Kuzyakov; Lena Q. Ma (Soil Biology and Biochemistry, 2025)

Shaping active transport behavior: The impact of public safety agencies and judicial institutions - Mengbing Du; Wen Li; Ning Qiu; Xiaoyang Liu (Journal of Transport Geography, 2025)

Bclaf1 mediates super-enhancer-driven activation of POLR2A to enhance chromatin accessibility in nitrosamine-induced esophageal carcinogenesis - Xiangjun Zhou; Xueqiong Zhou; Jun Li; Yingzheng He; Shizhen Qiu; Ye Xu; Zeyu Liu; Yina Yao; Jia Liu; Ying Wen; Sitong Xie; Jialong Chen; et al. (Journal of Hazardous Materials, 2025)

Prediction of peak discharge from earth–rock dam failures based on Bayesian optimization XGBoost regression algorithm - Ting Wang; Panrui Gao; Zhiwen Tian; Yanlong Li; Wen Qiu; Ning Shi; Zengguang Xu (Natural Hazards, 2025)

Nano-Selenium supplementation Improves Meat Quality, Protein Deposition, and Selenoprotein Gene Expression in Channel Catfish (Ictalurus Punctatus) - Zi Meng Li; Xiao Min Jin; Hui Long Qiu; Wen Hao Xu; Cong Hu; Ke Chen; Jia Qiang Huang; Lian Shun Wang (Biological Trace Element Research, 2025)

Re-understanding Sedimentary Characteristics of Shallow-water Delta in Funing Formation, Gaoyou Sag, Subei Basin, Eastern China - Zi-yi Yang; Gui-yu Dong; Lian-bo Zeng; Tian-zhuo Bi; Yong-feng Qiu; Hao Li; Xu Yang; Wen-long Qian; Mehdi Ostadhassan (Applied Geophysics, 2025)

Oxygen/sulfate radicals-generating CaS2O8 nanosonosensitizers induce PANoptosis and calcium overload for enhanced peritoneal metastasis immunotherapy - Qiang Wang; Yingfei Wen; Bo Bi; Kuan Li; Yuanqi Liu; Binbin Li; Shangbo Zhou; Zihang Li; Jiaqi Xu; Miaojuan Qiu; You Li; Meiying Wu; et al. (Science Bulletin, 2025)

Rational design of vitamin B3 derived bimetallic doped Cu-MOF with laccase-like activity for the colorimetric detection of Cr3+ - Xiao Liang; Qiu-Lan Li; Wen-Bo Zhao; De-Zhi Yang; Ya-Ling Yang; Zi-Tao Zhong (Journal of Environmental Chemical Engineering, 2025)

The Characterization, Biological Activities, and Potential Applications of the Antimicrobial Peptides Derived from Bacillus spp.: A Comprehensive Review - Jiaqi Zhang; Xinmiao Yang; Jiajia Qiu; Wen Zhang; Jie Yang; Jinzhi Han; Li Ni (Probiotics and Antimicrobial Proteins, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

A facile colorimetric sensor based on Fe3O4 magnetic nanoparticles with intrinsic catalytic activity for the rapid and selective detection of ochratoxin A - Xiao Liang; Qiu-Lan Li; Ji-Tao Li; Wen-Bo Zhao; De-Zhi Yang; Ya-Ling Yang; Zi-Tao Zhong (Food Chemistry, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Development of a novel low-temperature-tolerant microbial consortium for efficient degradation and recycling of farmland straw - Zhongxu Duan; Zhichao Kang; Xiangfen Kong; Guankai Qiu; Quanying Wang; Tianye Wang; Xuerong Han; Guopeng Zhu; Li Wen; Xingjian Xu; Youbo Su; Hongwen Yu (Journal of Environmental Chemical Engineering, 2025)

Decade-long application of preimplantation genetic testing for DMD/BMD: analysis of five clinical strategies and embryo recombination patterns - Weili Wang; Jing Dai; Xiao Hu; Wenbin He; Yifan Gu; Zhenxing Wan; Yi Zhang; Keli Luo; Wen Li; Qianjun Zhang; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2025)

The antinociceptive and anti-alpha-glucosidase effects of glucosides from Hemiphragma heterophyllum Wall. - Chun-Fang Wen; Yu-Xiao Li; Ke-Xin Nie; Qiu He; Ya Lu; Zi-Liang Wang; Xi-Shan Bai; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2025)

Monitoring the circumferential cracking of inner concrete core in prestressed concrete cylinder pipe during wire-wrapping using distributed optical fiber sensors - Shuai Liu; Yanlong Li; Ye Zhang; Minghui Ma; Wen Qiu; Lei She; Heng Zhou; Kangping Li; Kaiyu Sun (Tunnelling and Underground Space Technology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Construction of high-precision macromolecular model of Zhaozhuang anthracite based on microscopic level and optimization of surfactant applicability: Efficient control of coal dust - Wen Nie; Zhaoheng Xu; Ruoxi Li; Qiu Bao; Wenjin Niu; Qifan Tian; Xiaohan Zhang; Chenfeng Shi; Ke Tong; Zhihui Zhang (Process Safety and Environmental Protection, 2025)

Heterocyclic pseudoguaianolide oligomers and seco-pseudoguaianolide derivatives from the inflorescence of Ambrosia artemisiifolia - Zhi Zeng; Hua-liang He; Lin Qiu; Qiao Gao; Hong-shuai Gao; Jin Xue; Xiao-nian Li; You-zhi Li; Wen-bing Ding (Phytochemistry, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Environmental DNA/RNA metabarcoding for noninvasive and comprehensive monitoring and assessment of marine fishes - Peiyuan Ye; Jinping Cheng; Linus Shing Him Lo; Jingyu Liu; Chao Li; Kelvin Jun Yin So; Fei Xia; Meng Yan; Junjie Wang; Clara U; Jian-Wen Qiu; Wenlong Cai; et al. (Marine Pollution Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mathematical Model and Application of Overtopping Breach of Cascade earth-rock dams Considering Flood peak Enhancement Effect - Wen Qiu; Yanlong Li; Wei Zhao; Qiang Zhang; Lifeng Wen; Ye Zhang; Ting Wang (Water Resources Management, 2025)

Exaptation of pectoral fins for olfaction in the spiny red gurnard (Chelidonichthys spinosus) through an ancient receptor - Lisen Li; Deqian Fan; Chenglong Zhu; Zhuoya Liu; Wenji Huang; Peidong Xin; Huishan Yue; Mengying Li; Yufei Wang; Wenjie Xu; Jiangmin Zheng; Ye Li; et al. (Science China Life Sciences, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Synchronicity Between the Rates of Reaeration and Pollutants Degradation During Self-Purification in a Large River - Xin Wen; Qiu Jin; Jie Xu; Wei Yang; Huazu Liu; Chaowei Yuan; Shenhua Qian; Wei Li (Bulletin of Environmental Contamination and Toxicology, 2025)

Numerical Study on Hydrodynamic Performance and Vortex Dynamics of Multiple Cylinders Under Forced Vibration at Low Reynolds Number - Fulong Shi; Chuanzhong Ou; Jianjian Xin; Wenjie Li; Qiu Jin; Yu Tian; Wen Zhang (Journal of Marine Science and Engineering, 2025)
Flow around clustered cylinders is widely encountered in engineering applications such as wind energy systems, pipeline transport, and marine engineering. To investigate the hydrodynamic performance and vortex dynamics of multiple cylinders under forced vibration at low Reynolds numbers, with a focus on understanding the interference characteristics in various configurations, this study is based on a self-developed radial basis function iso-surface ghost cell computing platform, which improves the implicit iso-surface interface representation method to track the moving boundaries of multiple cylinders, and employs a self-constructed CPU/GPU heterogeneous parallel acceleration technique for efficient numerical simulations. This study systematically investigates the interference characteristics of multiple cylinder configurations across various parameter domains, including spacing ratios, geometric arrangements, and oscillation modes. A quantitative analysis of key parameters, such as aerodynamic coefficients, dimensionless frequency characteristics, and vorticity field evolution, is performed. This study reveals that, for a dual-cylinder system, there exists a critical gap ratio between X/D = 2.5 and 3, which leads to an increase in the lift and drag coefficients of both cylinders, a reduction in the vortex shedding periodicity, and a disruption of the wake structure. For a three-cylinder system, the lift and drag coefficients of the two upstream cylinders decrease with increasing spacing. On the other hand, this increased spacing results in a rise in the drag of the downstream cylinder. In the case of a four-cylinder system, the drag coefficients of the cylinders located on either side of the flow direction are relatively high. A significant increase in the lift coefficient occurs when the spacing ratio is less than 2.0, while the drag coefficient of the downstream cylinder is minimized. The findings establish a comprehensive theoretical framework for the optimal configuration design and structural optimization of multicylinder systems, while also providing practical guidelines for engineering applications.

DNA barcode reference database and gap analysis for biomonitoring Hong Kong’s marine animals - Mei-Hong Zhao; Jack Chi-Ho Ip; Chun Ming How; Yi-Xuan Li; Dumas Deconinck; Jian-Wen Qiu (Regional Studies in Marine Science, 2025)

Contrasting effects of arsenic on mycorrhizal-mediated silicon and phosphorus uptake by rice - Li-Xue Qiu; Ke-Xin Xu; Dong-Xing Guan; Yi-Wen Liu; Yu Luo; Xiang-Yu Zhu; H. Henry Teng; Yakov Kuzyakov; Lena Q. Ma (Journal of Environmental Management, 2025)

Petrogenesis of the unbrecciated pigeonite cumulate eucrite Northwest Africa 8326: Bridging the gap between eucrites and diogenites - Xiao-Wen Liu; Ai-Cheng Zhang; Li-Hui Chen; Lang Zhang; Xiao-Jun Wang; Jia Liu; Li-Ping Qin; Yu Liu; Qiu-Li Li; Xiao-Xiao Ling (Geochimica et Cosmochimica Acta, 2025)

Defect-rich α-MoC supported on nitrogen doped porous carbon for transformation of quinoline to aromatics - Zegang Qiu; Yuanzhe Wang; Zhiqin Li; Bo Ma; Chaoqiu Chen; Shuai Chen; Junqing Wen (Chemical Engineering Journal, 2025)

Genetic relationship analysis and fingerprint construction of some species in the genus Vanda (Orchidaceae) by interprimer binding site (iPBS) markers - Wen-Yi Yin; Xue-Qiang Cui; Qiu-Ju Zhao; Jie-Ling Deng; Chang-Yan Huang; Zi-Bin Zhang; Jia-Wei Li (Genetic Resources and Crop Evolution, 2025)

Transitional shale reservoir quality evaluation based on Random Forest algorithm—a case study of the Shanxi Formation, eastern Ordos Basin, China - Wanli Gao; Qin Zhang; Jingtao Zhao; Wen Liu; Weiliang Kong; Guangyin Cai; Tianquan Qu; Hongjie Peng; Wenyu Li; Yugang Yang; Yingfang Zhou; Zhen Qiu (Earth Science Informatics, 2025)

Ratiometric fluorescent paper chip for monitoring the freshness of high protein foods - Guobin Mao; Yuan Zeng; Chunmin Qiu; Guangmiao Ding; Leyao Li; Lixin Ma; Junbiao Dai; Wen Yin; Yingxin Ma (Analytica Chimica Acta, 2025)

Chinese advances in understanding and managing genitourinary tract infections caused by Mycoplasma genitalium, Mycoplasma hominis, and Ureaplasma urealyticum - Yanyan Qiu; Siyi Mao; Xianqi Li; Yinan Chen; Wenxin Chen; Yating Wen; Peng Liu (Archives of Microbiology, 2025)

Corrigendum: Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Effect of modified Fe2O3/activated carbon catalysts for low-temperature CO selective catalytic reduction of NOx in underground diesel vehicle exhaust - Wen Nie; Jie Lian; Yun Hua; Chengyi Liu; Xiao Yan; Qiu Bao; Wenjin Niu; Qifan Tian; Xiaohan Zhang; Ruoxi Li (Journal of Environmental Chemical Engineering, 2024)

Combined effects of benzene, toluene, xylene, ethylbenzene, and styrene exposure on hearing loss mediated by oxidative stress at realistic low levels - Yan Liu; Zihao Long; Jingjing Qiu; Qingfei Chen; Aichu Yang; Minghui Xiao; Shanfeng Dang; Yanqun Zhu; Qing Liu; Yanrong Lv; Shuangqi Li; Jingyao Qin; et al. (Environmental Pollution, 2024)

Synergy of chelating agents and surfactants on the wettability and pore structure of coal dust: Experimental study and molecular simulation - Wen Nie; Xiaohan Zhang; Wenjin Niu; Qiu Bao; Qifan Tian; Ruoxi Li; Chenfeng Shi; Ke Tong; Zhihui Zhang; Jie Lian (Chemical Engineering Journal, 2024)

Preparation and characterization of a low viscosity spray dust suppressant based on xanthan gum grafted sodium α-olefin sulfonate copolymer with proactive coal-adhesive and surface-active properties - Ruoxi Li; Wen Nie; Qiu Bao; Wenjin Niu; Qifan Tian; Xiaohan Zhang; Zhihui Zhang; Chenfeng Shi; Ke Tong (Chemical Engineering Journal, 2024)

Synchronous and efficient removal of carbon, nitrogen, and phosphorus from actual rural sewage by composite wetlands enhanced with functional fillers - Bing-Xu Guo; Wei-Yi Shi; Jun-Yu Ai; Ke-Jia Zhang; Qiu-Gang Wang; Wen-Huai Wang; Jun-Feng Li (Bioresource Technology, 2024)

Critical impact of pressure regulation on carbon dioxide biosynthesis - Yanqing Zhang; Yuxiang Liang; Hai Xiang; Pingli Li; Dongqing Zhan; Danna Ding; Shuangwei Du; Yangcheng Ding; Wen Liu; Xiawen Qiu; Huajun Feng (Bioresource Technology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Access to N-α-quaternary chiral morpholines via Cu-catalyzed asymmetric propargylic amination/desymmetrization strategy - Peng Chen; Mao-Mao Zhang; Li Rao; Yuan-Heng Li; Yue Jia; Ying Tan; Wen-Jing Xiao; Liang-Qiu Lu (Science Bulletin, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

PbHfO3-based antiferroelectric materials: Fundamentals, properties, and advanced applications - Dong-Liang Li; Xin-Gui Tang; Shui-Feng Li; Xiao-Bin Guo; Dan Zhang; Qi-Jun Sun; Wen-Hua Li; Zhen-Hua Tang; Yan-Ping Jiang; Qiu-Xiang Liu (Chemical Engineering Journal, 2024)

Triple-crosslinked double-network alginate/dextran/dendrimer hydrogel with tunable mechanical and adhesive properties: A potential candidate for sutureless keratoplasty - Wen Zhang; Shujing Liu; Lixiang Wang; Boxuan Li; Mengzhen Xie; Yingping Deng; Jialuo Zhang; Huazhang Zeng; Li Qiu; Lisha Huang; Tao Gou; Xiaobo Cen; et al. (Carbohydrate Polymers, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

Effectiveness of potential strategies to mitigate surface urban heat island: A comprehensive investigation using high-resolution thermal observations from an unmanned aerial vehicle - Sitao Li; Yi Zhu; Haokai Wan; Qiankun Xiao; Mingjun Teng; Wen Xu; Xiaogao Qiu; Xuefei Wu; Changguang Wu (Sustainable Cities and Society, 2024)

Imbalance of mitochondrial quality control regulated by STING and PINK1 affects cyfluthrin-induced neuroinflammation - Ji Zhao; Yi-kai Qiu; Yong-xing Xie; Xiao-yu Li; Yu-bin Li; Bing Wu; Yu-wen Wang; Xue-yan Tian; Yan-ling Lv; Ling-he Zhang; Wen-li Li; Hui-fang Yang (Science of The Total Environment, 2024)

Two ethylene-responsive transcription factors, AdVAL2 and AdKAN2, regulate early steps in kiwifruit starch degradation - Yang Tong; Wen-yue Su; Yu-tong Chen; Xiao-fen Liu; Qiu-yun Zhang; Tong-hui Qi; Andrew C. Allan; Xiang Li; Xue-ren Yin (Postharvest Biology and Technology, 2024)

Qualitative analysis of hydrophilic headgroup water molecular space dependence and wetting effects of solution systems on polluting coal dust - Qiu Bao; Wen Nie; Wenjin Niu; Ilele Felicie Mwabaima; Stephen Nyabire Akanyange; Qifan Tian; Ruoxi Li (Journal of Environmental Chemical Engineering, 2024)

Curcumin loaded high internal phase emulsions: Formulation and potential to alleviate DSS-induced ulcerative colitis - Xiao-Long Li; Bao-Qiu Yang; Wen-Jie Liu; Han Tao; Bao Zhang (Food Bioscience, 2024)

Multifunctional chitosan-based hydrogels loaded with iridium nanoenzymes for skin wound repair - Ruoying Wang; Shixin Xu; Miaomiao Zhang; Wei Feng; Chengwei Wang; Xuefeng Qiu; Jierui Li; Wen Zhao (Carbohydrate Polymers, 2024)

Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)
The coral reefs along Pakistan’s coastline are of ecological and economic significance. However, they are increasingly threatened by anthropogenic threats and climate change. These vulnerable ecosystems are declining due to various factors such as sedimentation, climate change, overfishing, destructive fishing practices, marine pollution, and tourism development. We found that 29%, 24%, 26%, 16% and 18% of the studies exceeding, marine pollution, overfishing/destructive fishing, coastal tourism, climate change and sedimentation, respectively; thus, indicating inadequate water quality status in part of Pakistan coastal water. These influences lead to several negative impacts, such as jeopardized coral health, decline in biodiversity, and the simplification of reef structures. In response to these threats, conservation efforts are imperative. This literature review provides an in-depth analysis of anthropogenic threats, climate change and the conservation of coral reefs in Pakistan. This review provides suggestions on how the country could better conserve its coral reef ecosystem. These include (1) initiatives such as establishing marine protected areas (MPAs), (2) encouraging sustainable fishing practices and reducing pollution, (3) developing the country as an ecotourism destination and implementing climate change adaptation measures, and (4) community engagement through awareness campaigns and fostering collaboration among, governmental organizations, non-governmental organizations (NGOs) and scientists. These comprehensive conservation policies address human-caused and other challenges, safeguarding their ecological, economic, and cultural relevance for future generations.

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

A systematic review of the physiological and environmental impacts of coal dust and its control technologies - Stephen Nyabire Akanyange; Wen Nie; Felicie Ilele Mwabaima; Fei Liu; Wenjin Niu; Si-qi Jiang; Yan Zhang; Gifty Adom-Asamoah; Martin Luther Yeboah; Bao Qiu; Haoming Li (Fuel, 2024)

Design of multifunctional theranostic nanoplatforms with glutathione-triggered H2S generation and H2S-activitated multi-modal therapy - Cheng Tao; Qian Ren; Nuo Yu; Mei Wen; Pu Qiu; Shining Niu; Zhigang Chen; Kun Li; Dong Xie (Chemical Engineering Journal, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Soil water consumption along the profile in response to soil water content variations in a black locust plantation with a rainfall exclusion in Loess Plateau - Mei-Jun Liu; Le Chang; Qiu-Wen Chen; Guoqing Li; Sheng Du (Journal of Hydrology, 2024)

Integrated whole genome sequencing and transcriptomic analysis reveal the biodegradation mechanism of vanillic acid in Herbaspirillum aquaticum KLS-1 - Yong-He Han; Yi-Xi Li; Wen-Qian Qiu; Xi-Wen Cui; Xian Chen; Yong Zhang; Hong Zhang; Shan-Shan Wang (Journal of Environmental Chemical Engineering, 2024)

Phelligridimer A enhances the expression of mitofusin 2 and protects against cerebral ischemia/reperfusion injury - Xing Li; Bingtian Xu; Lu Long; Yuting Li; Xuan Xiao; Shuqin Qiu; Jiangping Xu; Li-Wen Tian; Haitao Wang (Chemico-Biological Interactions, 2024)

The emerging and legacy persistent organic contaminants in corals of the South China Sea - Yao-Wen Qiu; Jun Li; Mei-Xia Zhao; Ke-Fu Yu; Gan Zhang (Chemosphere, 2024)

The coupling of sulfide and Fe-Mn mineral promotes the migration of lead and zinc in the redox cycle of high pH floodplain soils - Qianqian Yu; Junwei Wen; Sili Zhang; Chen Wu; Hao Ouyang; Nannan Hu; Xu Li; Xinhong Qiu (Journal of Hazardous Materials, 2024)

Network-expandable polydimethylsiloxane for cost-free enhanced droplet yield and smart temperature control in microfluidics - Limin Zhang; Yonggan Yan; Yuan Li; Xiang Shi; Lichao Xia; Qi Wen; Luxing Wei; Xiaoyong Qiu; Xiaolai Zhang; Xin Cui; Jing Liu; Jun Huang (Chemical Engineering Journal, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

Fabrication and characterization of emulsion-template oleogels assembled from octenyl succinic anhydride starch/chitosan electrostatic complexes - Wenbo Miao; David Julian McClements; Zhiheng Zhang; Qianzhu Lin; Hangyan Ji; Jinpeng Wang; Zhengyu Jin; Guanghua Li; Liming Jiang; Jinsheng Wen; Shangyuan Sang; Chao Qiu (Food Hydrocolloids, 2024)

Experimental and simulation studies on the improvement of coal dust pollution by an aqueous solution of sodium α-alkenylsulfonate and amino acid-based surfactants - Huajun Liu; Wen Nie; Qifan Tian; Qiu Bao; Wenjin Niu; Ruoxi Li; Xiaohan Zhang; Stephen Nyabire Akanyange (Environmental Pollution, 2024)

Numerical investigation on the evolution process of cascade dam-break flood in the downstream earth-rock dam reservoir area based on coupled CFD-DEM - Wen Qiu; Yanlong Li; Ye Zhang; Lifeng Wen; Ting Wang; Jing Wang; Xinjian Sun (Journal of Hydrology, 2024)

Full-spectrum-responsive Ti4O7-PVA nanocomposite hydrogel with ultrahigh evaporation rate for efficient solar steam generation - Xinye Xu; Qi Zhao; Qi Liu; Junxiao Qiu; Jinhao Li; Wenqian Zheng; Jie Cao; Lina Wang; Wen Wang; Shutong Yuan; Anni Fu; Hanjun Yang; et al. (Desalination, 2024)

The biocontrol potentials of rhizospheric bacterium Bacillus velezensis K0T24 against mulberry bacterial wilt disease - Wenlian Jiao; Ju Wen; Na Li; Ting Ou; Changyu Qiu; Yutong Ji; Kai Lin; Xiaojiao Liu; Jie Xie (Archives of Microbiology, 2024)

Inulin alleviates perinatal 2-ethylhexyl diphenyl phosphate (EHDPHP) exposure-induced intestinal toxicity by reshaping the gut microbiota and suppressing the enteric-origin LPS/TLR4/NF-κb pathway in dams and pups - Xiu-Wen Li; Feng Qiu; Yi Liu; Jian-Zheng Yang; Li-Jian Chen; Jia-Hao Li; Jia-Li Liu; Clare Hsu; Long Chen; Jia-Hao Zeng; Xiao-Li Xie; Qi Wang (Environmental Pollution, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Bio-based ionic liquid filter with enhanced electrostatic attraction for outside filtration and inside collection of viral aerosols - Guo-Hao Zhang; Qiu-Hong Zhu; Lei Zhang; Lei Li; Jie Fu; Shuang-Long Wang; Wen-Li Yuan; Ling He; Guo-Hong Tao (Journal of Hazardous Materials, 2024)

Revealing the role of crystal chemistry in REE fractionation in skarn garnets: insights from lattice-strain theory - Guang Wen; Jun Qiu; Albert H. Hofstra; Daniel E. Harlov; Zhe Ren; Jian-Wei Li (Contributions to Mineralogy and Petrology, 2024)

Enzymatically prepared neoagarooligosaccharides improve gut health and function through promoting the production of spermidine by Faecalibacterium in chickens - A La Teng Zhu La; Depeng Li; Zhiqian Cheng; Qiu Wen; Die Hu; Xiaolu Jin; Dan Liu; Yuqing Feng; Yuming Guo; Gong Cheng; Yongfei Hu (Science of The Total Environment, 2024)

Geochemical prospectivity mapping using compositional balance analysis and multifractal modeling: A case study in the Jinshuikou area, Qinghai, China - Chao Li; Kefa Zhou; Wen Gao; Xianrong Luo; Zhihua Tao; Panfeng Liu; Wei Qiu (Journal of Geochemical Exploration, 2024)

Kinetic studies of the secondary hydrate formation in porous media based on experiments in a cubic hydrate simulator and a new kinetic model - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yi-Song Yu; Qiu-Nan Lv; Yang Yu; Yi-Fan Weng; Jian-Wu Liu; Jian-Xing Yu (Fuel, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Application of solid electrolytes in electrochemical reduction of CO2 or O2 - Jiayue Li; Zhuowen Wang; Sibei Liu; Zhonglin Chen; Jixian Yang; Zhiqiang Chen; Ang Li; Qinxue Wen; Li Wang; Shan Qiu; Chongwei Cui; Huiyuan Deng; et al. (Chemical Engineering Journal, 2024)

The remediation potential and kinetics of Pb2+ adsorbed by the organic frameworks of Cladophora rupestris - Lu-sheng Zhang; Xiao-yu Feng; Chang-fa Qiu; Ling-sheng Li; Yu Sun; Xin-yi Tao; Xin-yue Li; Zhao-wen Liu; De-ju Cao (Environmental Science and Pollution Research, 2024)

Are microplastics in livestock and poultry manure an emerging threat to agricultural soil safety? - Yuannan Long; You Zhang; Zhenyu Zhou; Ruyi Liu; Ziyi Qiu; Yiming Qiu; Juan Li; Wenming Wang; Xiwei Li; Lingshi Yin; Xiaofeng Wen (Environmental Science and Pollution Research, 2024)

Microplastics exposure induced and exacerbated the development of systemic lupus erythematosus in mice - Huinan Chen; Li Wan; Yiwu Qiu; Fuhai Qiu; Chengping Wen; Yingying Mao; Zhixing He (Science of The Total Environment, 2024)

Meroterpenoids with divers' rings systems from Phyllosticta capitalensis and their anti-inflammatory activity - Xiao-xia Zhu; Wan-qiu Liu; Zhao-xia Shi; Huang-yao Zhu; Si-qi Fan; Jie Zhang; Wen-yuan Liu; Li-Jun Xu; Qing-Jia Ren; Feng Feng; Jian Xu (Phytochemistry, 2024)

A novel strategy for designing the lithium powder anode stabilized by electrospun membrane for lithium metal batteries with high specific energy - Huihui Gan; Ye Xia; Jiajun Sun; Pengyuan Qiu; Liang Li; Wen Zhu (Chemical Engineering Journal, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Molecular simulation and wetting study on the mechanism and capability of hydrophilic surfactants used as spray dust suppressants for dust reduction in coal mines - Qiu Bao; Wen Nie; Wenjin Niu; Ilele Felicie Mwabaima; Qifan Tian; Ruoxi Li (Sustainable Chemistry and Pharmacy, 2023)

The joint association of ambient air pollution and different sleep posture with mild obstructive sleep apnea: A study conducted at Taipei Sleep Center - Yansu He; Wen-Te Liu; Shangyang Lin; Zhiyuan Li; Hong Qiu; Steve Hung Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Characterization and biocontrol mechanism of Streptomyces olivoreticuli as a potential biocontrol agent against Rhizoctonia solani - Jie Zhong; Wen Wen Sui; Xin Yi Bai; Ze Lan Qiu; Xiao Gang Li; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Daily and seasonal patterns of stem diameter micro-variations in three semiarid forest species in relation to water status and environmental factors - Mei-Jun Liu; Qiu-Wen Chen; Hai-Ning Guo; Jinlin Lyu; Guoqing Li; Sheng Du (Dendrochronologia, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The essential oil of Kochia scoparia (L.) Schrad. as a potential repellent against stored-product insects - Yang Wang; Xiao-Kun Bian; Li Zhang; Wen-Yan Chen; Qiu-Ju Lyu; Shu-Shan Du (Environmental Science and Pollution Research, 2023)

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

In situ enrichment of sulphate-reducing microbial communities with different carbon sources stimulating the acid mine drainage sediments - Zhuo-hui Wu; Xiao-dan Yang; Li-ying Huang; Shi-lin Li; Fei-yun Xia; Yong-zhi Qiu; Xin-zhu Yi; Pu Jia; Bin Liao; Jie-Liang Liang; Wen-sheng Shu; Jin-tian Li (Science of The Total Environment, 2023)

Perovskites with narrow quantum-wells distribution and thermally activated energy funneling for sky-blue light-emitting diodes - Guanwei Sun; Weidong Qiu; Jiayu Li; Shuai Zhang; Zijian Chen; Denghui Liu; Chenyang Shen; Tao Wen; Zhe Liu; Junrong Pu; Zhihai Yang; Guo-xi Yang; et al. (Chemical Engineering Journal, 2023)

Interactions between fluorocarbon surfactant and coal dust at macro, meso and molecular scales and their applications in coal dust control - Wenjin Niu; Wen Nie; Qiu Bao; Qifan Tian; Fei Liu; Ruoxi Li; Xiaohan Zhang; Felicie Mwabama Ilele; Stephen Nyabire Akanyange (Chemical Engineering Journal, 2023)

Nanoscale evidence of zircon-coffinite-xenotime solid solution observed by atom probe tomography - Wenhao Zhao; Bi-Wen Wang; Li-Xin Gu; Xu Tang; Yu Liu; Muhammad Awais; Xiao-Chi Liu; Xian-Hua Li; Rong Hu; Qiu-Li Li (Chemical Geology, 2023)

Effect of seepage-induced erosion on soil macropore structure - Wen-bo Huang; Da Huang; Yi-kang Gao; Yang Liu; Zhao Li; Qiu-jie Meng (Journal of Mountain Science, 2023)

Coupling heat transfer study of liquid sodium and supercritical carbon dioxide in a PCHE straight channel based on a four-equation model - Xing-Kang Su; Xian-Wen Li; Xiang-Yang Wang; Qi-Jian Chen; Qian-Wan Shi; Jing Qiu; Long Gu (Annals of Nuclear Energy, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Study on electrothermal ignition model of self-propagation high-temperature synthesis system for samarium vaporization - Yanshuai Zheng; Kun Xue; Yang Qiu; Zheng-Wen Xu; Hai-Sheng Zhao; Ju-Tao Yang; Shouzhi Xie; Hai-Ying Li (Advances in Space Research, 2023)

Three new compounds from Anoectochilus roxburghii (Wall.) Lindl - Yan-Lin Bin; Shun-Zhi Liu; Ting-Ting Xie; Wen-Zheng Feng; Hao-Yang Li; Zi-Jia Ye; Zhi-Hao Dong; Ying-Kun Qiu (Natural Product Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Enhancing degradation of norfloxacin using chrysanthemum-shaped bimetallic NH2-MIL-53(Fe/Ti) photocatalysts under visible light irradiation - Wen Gao; Fangyuan Wang; Meilin Ou; Qianqian Wu; Lei Wang; Haonan Zhu; Yuanyuan Li; Ning Kong; Jianping Qiu; Shanshan Hu; Shuang Song (Journal of Environmental Chemical Engineering, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Non-Eutectic-Salt Reaction Route towards Morphological and Structural Rearrangement of Li-Rich Layered Oxides for High-Volumetric Li-Ion Batteries - Tingting Li; Zhepu Shi; Li Li; Yibin Zhang; Ying Li; Jialiang Zhao; Qingwen Gu; Wen Wen; Bao Qiu; Zhaoping Liu (Chemical Engineering Journal, 2023)

Thienoacene-fused fluorophores for highly efficient deep red/near-infrared OLEDs - Li Zhu; Yixia Liu; Xiaofei Wang; Kai Zhang; Jing-Wen Tai; Yan-Qiu Sun; Chuan-Kui Wang; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2023)

Trichoscopy for early diagnosis and follow-up of pet-related neonatal tinea capitis - Hui-Lin Zhi; Xiu-Jiao Xia; Hong Shen; Wen-Wen Lv; Yan Zhong; Bo Sang; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2023)

Imbalance of multiple neurotransmitter pathways leading to depression-like behavior and cognitive dysfunction in the triple transgenic mouse model of Alzheimer disease - Meng Zhang; Li-yuan Liu; Yong Xu; Wen-zhi Wang; Nian-zhuang Qiu; Fang-fang Zhang; Feng Zhang; Xiao-dan Wang; Wei Chen; Xiao-yan Xu; Yong-feng Gao; Mei-hua Chen; et al. (Metabolic Brain Disease, 2023)

Study of wetting and adsorption mechanism of mixed anionic-nonionic nonhomologous surfactants on coal dust based on intermolecular interactions - Wen Nie; Ruoxi Li; Wenjin Niu; Qiu Bao; Qifan Tian; Xiaohan Zhang; Xiao Yan; Jie Lian (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A chemotactic microrobot with integrated iridescent surface for optical-tracking - Yuzhao Zhang; Jingang Wang; Haibo Yu; Jianchen Zheng; Xiubao Zhao; Hongji Guo; Ye Qiu; Xiaoduo Wang; Lianqing Liu; Wen Jung Li (Chemical Engineering Journal, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Air pollution exacerbates mild obstructive sleep apnea by disrupting nocturnal changes in lower-limb body composition: a cross-sectional study conducted in urban northern Taiwan - Yansu He; Wen-Te Liu; Shang-Yang Lin; Zhiyuan Li; Hong Qiu; Steve Hung-Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Holocene variations in the Asian Summer and Winter Monsoons reconstructed from extensive lacustrine sediments in the Mu Us Desert, northern China - Xiaohao Wen; Matt W. Telfer; Baosheng Li; Wei Wang; Tim Daley; Chen Wang; Mengyuan Tian; Mingkun Qiu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Applying mass flow analysis and aeration optimization strategy to reduce energy consumption of a full-scale anaerobic/anoxic/oxic system - Lu-Man Jiang; Wen Zhang; Yunhui Li; Yanjun Shao; Zhenjian Zhang; Ming Zhang; Junli He; Ji Qiu; Wenxiang Li; Junwei Wang; Zhen Zhou (Journal of Water Process Engineering, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Breakup mechanism of the northern South China Sea: Evidence from the deep crustal structure across the continent-ocean transition - Qiang Wang; Minghui Zhao; Jiazheng Zhang; Haoyu Zhang; Jean-Claude Sibuet; Zizheng Li; Enyuan He; Xuelin Qiu; Wen Peng; Guizhong Chen (Gondwana Research, 2023)

Development and characterization of a high efficiency bio-based rhamnolipid compound dust suppressant for coal dust pollution control - Wenjin Niu; Wen Nie; Qiu Bao; Qifan Tian; Ruoxi Li; Xiaohan Zhang; Xiao Yan; Jie Lian (Environmental Pollution, 2023)

Effect of Bacillus amyloliquefaciens LSG2 ‐8 on the intestinal barrier function of Amur minnow ( Rhynchocypris lagowskii ) - Meng‐Nan Yu; Wen‐li Zhu; Si‐bu Wang; Dong‐Ming Zhang; Yu‐Rou Zhang; Qiu‐Ju Wang; Gui‐Qin Wang; Mahmoud M. Elsadek; Qi Yao; Yu‐Ke Chen; Zhi‐Xin Guo (Journal of Fish Biology, 2023)
Probiotics are widely used in aquaculture. This article aims to study the effect of Bacillus amyloliquefaciens LSG2‐8 on the intestinal barrier function of Rhynchocypris lagowskii. B. amyloliquefaciens LSG2‐8 were added to R. lagowskii basal diets (CK) as additives at four concentrations: 1.0 × 10 6 (D‐6), 1.0 × 10 7 (D‐7), 1.0 × 10 8 (D‐8) and 1.0 × 10 9 (D‐9) CFU g −1 by dry weight of basal diet. After a 56‐day feeding experiment, the activities of intestinal digestive enzymes and immunity‐related enzymes of R. lagowskii on group D‐6, D‐7, D‐8 and D‐9 diet were significantly higher than the control ( P R. lagowskii were significantly higher ( P R. lagowskii on group D‐6, D‐7, D‐8 and D‐9 diet were significantly lower than those of the control ( P B. amyloliquefaciens LSG2‐8 can regulate the intestinal flora balance and improve the intestinal structure of R. lagowskii . In conclusion, B. amyloliquefaciens LSG2‐8 can improve the intestinal barrier function of R. lagowskii and can be used as a feed additive in aquaculture.

In situ cross-linked fluorinated gel polymer electrolyte based on PEGDA-enabled lithium-ion batteries with a wide temperature operating range - Han He; Yue Wang; Meng Li; Jingyi Qiu; Yuehua Wen; Junhong Chen (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Study on the effect of Ce–Cu doping on Mn/γ-Al2O3 catalyst for selective catalytic reduction in NO with NH3 - Wen Nie; Xiao Yan; Fengning Yu; Qiu Bao; Na Li; Weiwei Zhou; Wenjin Niu; Qifan Tian (Environmental Geochemistry and Health, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Revisiting paleoenvironmental changes on the Upper Yangtze Block during the Ordovician-Silurian transition: New insights from elemental geochemistry - Zhen Qiu; Yifan Li; Wei Xiong; Tailiang Fan; Qun Zhao; Qin Zhang; Yuman Wang; Wen Liu; Feng Liang; Jiaqiang Zhang; Gary Lash (Sedimentary Geology, 2023)

Petrographic and geochemical characteristics of the Middle−Upper Cambrian Xixiangchi dolomites in the central Sichuan Basin, southwest China: Implications for dolomite origins and dolomitization mechanisms - Jintong Liang; Karem Azmy; Kunyu Li; Sibing Liu; Luping Li; Gang Zhou; Yuchao Qiu; Wenzheng Li; Yuan He; Huaguo Wen (Marine and Petroleum Geology, 2023)

Synergistic effect of binary mixture of anionic nonionic surfactant on inhibiting coal dust pollution: Experiment and simulation - Wen Nie; Qifan Tian; Wenjin Niu; Ruoxi Li; Qiu Bao; Xiaohan Zhang; Xiao Yan; Jie Lian (Journal of Environmental Chemical Engineering, 2023)

Deficiency of Lactoferrin aggravates lipopolysaccharide-induced acute inflammation via recruitment macrophage in mice - Can Liu; Qiu Peng; Lingyu Wei; Zhengshuo Li; Xiaoyue Zhang; Yangge Wu; Jia Wang; Xiang Zheng; Yuqing Wen; Run Zheng; Qun Yan; Qiurong Ye; et al. (BioMetals, 2023)

Numerical study on conjugate heat transfer characteristics of liquid lead-bismuth eutectic and supercritical carbon dioxide in a PCHE straight channel - Xing-Kang Su; Xian-Wen Li; Xiang-Yang Wang; Qi-Jian Chen; Qian-Wan Shi; Jing Qiu; Long Gu (Annals of Nuclear Energy, 2023)

Surface-enhanced Raman spectroscopy charged probes under inverted superhydrophobic platform for detection of agricultural chemicals residues in rice combined with lightweight deep learning network - Shizhuang Weng; Le Tang; Mengqing Qiu; Jinghong Wang; Yehang Wu; Rui Zhu; Cong Wang; Pan Li; Wen Sha; Dong Liang (Analytica Chimica Acta, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Preparation, characterization and safety evaluation of Ligusticum chuanxiong essential oils liposomes for treatment of cerebral ischemia-reperfusion injury - Yu Long; Shuang Yu; Dan Li; Ai Shi; Yin Ma; Jie Deng; Xiao-qiu Li; Jing Wen; Yuan-yuan Wu; Yue Hu; Xiao-fang He; Nan Li; et al. (Food and Chemical Toxicology, 2023)

A new species of the genus Catillopecten (Bivalvia: Pectinoidea: Propeamussiidae): morphology, mitochondrial genome, and phylogenetic relationship - Yi-Tao Lin; Yi-Xuan Li; Yanan Sun; Jun Tao; Jian-Wen Qiu (Frontiers in Marine Science, 2023)
Catillopecten is a small genus of deep-sea glass scallops, but its diversity is poorly known in many parts of the world ocean. We described C. margaritatus n. sp. (Pectinoidea: Propeamussiidae), and performed morphological analyses and DNA sequencing, and estimated the divergence time of scallops based on samples collected from Haima cold seep in the South China Sea. Morphologically, the new species can be distinguished from congeneric species by its large shell size, relatively small auricle length, absence of monocrystal aerials, presence of longitudinal radial ridges on the left valve, and the alternated rounded striae and distal and proximal growth lines of prisms on the right valve. Anatomically, this new species can be distinguished from C. vulcani by its anteriorly located auriculate gills, compared to the centrally located lamellar gills of the latter, and the different locations of the pericardium. Sequence comparison and phylogenetic analysis based on the 18S rRNA fragments supported the placement of the new species in Catillopecten . We also report the mitogenome of C. margaritatus n. sp. as the only reported mitogenome of the family Propeamussiidae, which differs from those of other scallops substantially in gene order arrangement. Divergence time estimation revealed that Propeamussiidae and Pectinidae diverged in the early Carboniferous, while Catillopecten and Parvamussium diverged during the late Cretaceous to early Eocene. Finally, we presented a key to the species of Catillopecten .

Experimental study on the longitudinal evolution of the overtopping breaching of concrete-face sand-gravel dams - Wen Qiu; Yanlong Li; Lifeng Wen; Lin Wang; Zengguang Xu (Bulletin of Engineering Geology and the Environment, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Spatial distribution and inventory of natural gas hydrate in the Qiongdongnan Basin, northern South China Sea - Zhongxian Zhao; Ning Qiu; Zhen Sun; Wen Yan; Genyuan Long; Pengchun Li; Haiteng Zhuo (Journal of Oceanology and Limnology, 2023)

Inhibition of perilipin 2 attenuates cerebral ischemia/reperfusion injury by blocking NLRP3 inflammasome activation both in vivo and in vitro - Xu-Ying Liu; Qiu-Shi Li; Wen-Hai Yang; Yue Qiu; Fei-Fei Zhang; Xiu-Hui Mei; Qi-Wen Yuan; Ru-Bo Sui (In Vitro Cellular & Developmental Biology - Animal, 2023)

Refined mathematical model for the breaching of concrete-face sand-gravel dams due to overtopping failure - Wen Qiu; Yan-long Li; Li-feng Wen; Jing Wang; Qiao-gang Yin (Journal of Mountain Science, 2023)

Editorial: Deep-sea chemosynthetic ecosystems: Living in extreme environments - Hao Chen; Chaolun Li; Jian-Wen Qiu; Raul Bettencourt; Dong Feng; Yong Wang; Hongmei Jing; Jin Sun (Frontiers in Marine Science, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Key factors controlling the kinetics of secondary hydrate formation in the porous media - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yang Yu; Yi-Fan Weng; Qiu-Nan Lv; Jian-Xing Yu (Gas Science and Engineering, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Effects of β-amylase hydrolysis on the structural, physicochemical and storage properties of wheat starch - Yan Li; Wen Cheng; Xi Qiu; Yujie Sun; Xuanze Xia; Lianzhan Yang; Mingcong Fan; Li Wang; Haifeng Qian (Journal of Cereal Science, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Effects of Toxin-Antitoxin System HicAB on Biofilm Formation by Extraintestinal Pathogenic E. coli - Bo Hou; Chen-Yan Wang; Shao-Wen Li; Lun-Jiang Zhou; Yong-Liang Che; Qiu-Yong Chen (Current Microbiology, 2023)

A1 Adenosine Receptor Activation Inhibits P2X3 Receptor–Mediated ATP Currents in Rat Dorsal Root Ganglion Neurons - Jia-Wei Hao; Wen-Long Qiao; Qing Li; Shuang Wei; Xue-Mei Li; Ting-Ting Liu; Chun-Yu Qiu; Wang-Ping Hu (Molecular Neurobiology, 2022)

Green surfactant-modified TiO2 nanoparticles doped with La-Cr bimetal for NOx removal - Wen Nie; Weiwei Zhou; Na Li; Yun Hua; Qiu Bao; Jiayi Yan; Mingyue Yuan; Cheng Guo; Fengning Yu; Wenjin Niu; Chengyi Liu (Environmental Science and Pollution Research, 2022)

The correlation of CD70 in immune characteristics and drug therapy of pan-cancer - Yang Yang; Jinghong Chen; Mingyang Feng; Yujiao Wang; Weiting Liao; Qiuji Wu; Feng Wen; Qiu Li (Human Cell, 2022)

Experimental study on the process of overtopping breach of concrete-faced sand-gravel dam - Yanlong Li; Wen Qiu; Zuyu Chen; Lifeng Wen; Lin Wang (European Journal of Environmental and Civil Engineering, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Bedside Diagnosis for Disseminated Deep Dermatophytosis: a Case Series Study - Xiu-Jiao Xia; Hong Shen; Hui-Lin Zhi; Yan Zhong; Bo Sang; Wen-Wen Lv; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Morphological and Molecular Characterization of Paragonimus skrjabini Complex from Yunnan, China: A Brief Report - Qiu-Hong Shu; Shu-De Li; Ming Tian; Yong Meng; Shu-Mei-Qi He; Min Zhu; Miao-Miao Wang; Wen-Lin Wang (Acta Parasitologica, 2022)
Purpose To perform environmental sampling and molecular identification of Paragonimus in endemic regions, which may help in minimizing transmission among humans. Methods Mountain crabs from the genus Potamiscus were collected and the encysted metacercariae were extracted and subjected to morphological identification, followed by animal inoculation in Sprague–Dawley (SD) rats. After 112 days of infection, animals were killed and adult worms were extracted from lungs and muscles. The morphology of adult worms was characterized by microscopy and molecular identification was done by polymerase chain reaction, followed by sequencing of cox1 and ITS2 genes. Phylogenetic analysis was done by maximum parsimony method. Results A total of 447 crabs were captured from the streams of Tongchang Town, Jinping County, Yunnan Province, China. The infection rate was found to be 41% (186 out of 447 crabs). The metacercariae of Paragonimus skrjabini was identified by the characteristics round or spherical encysted form measuring 410 to 460 × 400 to 460 µm. After animal infection in SD rats, adults were presumptively confirmed to be P. skrjabini , which was also confirmed by gene amplification and sequence analysis of cox1 and ITS2 regions. Paragonimus skrjabini clustered with previously reported P. skrjabini from Yunnan and Vietnam. The confidence values of their branches were > 95%. Phylogenetic analysis of the ITS2 region revealed two distinct clusters with distinct geographical grouping. Phylogenetic analysis with the combined data sets reiterated the geographical grouping with P. skrjabini from Yunnan clustering with strains from Vietnam. Conclusion Metacercariae of P. skrjabini was discovered in freshwater crabs in Yunnan province, China, and the strains were phylogenetically related to P. skrjabini from Vietnam.

Indicator species drive the key ecological functions of microbiota in a river impacted by acid mine drainage generated by rare earth elements mining in South China - Ziwu Chen; Xi Zhong; Mengyuan Zheng; Wen‐Shen Liu; Yingheng Fei; Kengbo Ding; Yaying Li; Ye Liu; Yuanqing Chao; Ye‐Tao Tang; Shizhong Wang; Rongliang Qiu (Environmental Microbiology, 2022)
Summary Acid mine drainage (AMD) generated by rare earth elements (REEs) deposits exploration contains high concentrations of REEs, ammonium and sulfates, which is quite different from typical metallic AMD. Currently, microbial responses and ecological functions in REEs‐AMD impacted rivers are unknown. Here, 16S rRNA analysis and genome‐resolved metagenomics were performed on microbial community collected from a REEs‐AMD contaminated river. The results showed that REEs‐AMD significantly changed river microbial diversity and shaped unique indicator species (e.g. Thaumarchaeota , Methylophilales , Rhodospirillales and Burkholderiales ). The main environmental factors regulating community were pH, ammonium and REEs, among which high concentration of REEs increased REEs‐dependent enzyme‐encoding genes ( XoxF and ExaF / PedH ). Additionally, we reconstructed 566 metagenome‐assembled genomes covering 70.4% of identifying indicators. Genome‐centric analysis revealed that the abundant archaea Thaumarchaeota and Xanthomonadaceae were often involved in nitrification and denitrification, while family Burkholderiaceae were capable of sulfide oxidation coupled with dissimilatory nitrate reduction to ammonium. These indicators play crucial roles in nitrogen and sulfur cycling as well as REEs immobilization in REEs‐AMD contaminated rivers. This study confirmed the potential dual effect of REEs on microbial community at the functional gene level. Our investigation on the ecological roles of indicators further provided new insights for the development of REEs‐AMD bioremediation.

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Using computational fluid dynamic simulation with Flow-3D to reveal the origin of the mushroom stone in the Xiqiao Mountain of Guangdong, China - Jian-cheng Li; Wei Wang; Yan-ming Zheng; Xiao-hao Wen; Jing Feng; Li Sheng; Chen Wang; Ming-kun Qiu (Journal of Mountain Science, 2022)

Responses of soil pH to no‐till and the factors affecting it: A global meta‐analysis - Xin Zhao; Cong He; Wen‐Sheng Liu; Wen‐Xuan Liu; Qiu‐Yue Liu; Wei Bai; Li‐Jun Li; Rattan Lal; Hai‐Lin Zhang (Global Change Biology, 2022)
No‐till (NT) is a sustainable option because of its benefits in controlling erosion, saving labor, and mitigating climate change. However, a comprehensive assessment of soil pH response to NT is still lacking. Thus, a global meta‐analysis was conducted to determine the effects of NT on soil pH and to identify the influential factors and possible consequences based on the analysis of 114 publications. When comparing tillage practices, the results indicated an overall significant decrease by 1.33 ± 0.28% in soil pH under NT than that under conventional tillage ( p −1 (−1.83%), or crop residue retention (−1.52%). Changes in organic matter decomposition under undisturbed soil and with crop residue retention might lead to a higher concentration of H + and lower of basic cations (i.e., calcium, magnesium, and potassium), which decrease the soil pH, and consequently, impact nutrient dynamics (i.e., soil phosphorus) in the surface layer under NT. Furthermore, soil acidification may be aggravated by NT within site‐specific conditions and improper fertilizer and crop residue management and consequently leading to adverse effects on soil nutrient availability. Thus, there is a need to identify strategies to ameliorate soil acidification under NT to minimize the adverse consequences.

Inhibition of Maternal c-Src Ameliorates the Male Offspring Hypertension by Suppressing Inflammation and Neurotransmitters in the Paraventricular Nucleus - Qing Su; Xiao-Jing Yu; Qing Yang; Xiao-Min Wang; Wen-Jie Xia; Hong-Bao Li; Kai-Li Liu; Qiu-Yue Yi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Genomic and transcriptomic insights into the habitat adaptation of the diazotrophic paddy‐field cyanobacterium Nostoc sphaeroides - Zhen Chen; Jin‐Long Shang; Shengwei Hou; Tao Li; Qi Li; Yi‐Wen Yang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Nitrogen‐fixing cyanobacteria are common in paddy fields, one of the most productive wetland ecosystems. Here, we present the complete genome of Nostoc sphaeroides, a paddy‐field diazotroph used for food and medicine for more than 1700 years and deciphered the transcriptional regulation during the developmental transition from hormogonia to vegetative filaments with heterocysts. The genome of N. sphaeroides consists of one circular chromosome (6.48 Mb), one of the largest ever reported megaplasmids (2.34 Mb), and seven plasmids. Multiple gene families involved in the adaption to high solar radiation and water fluctuation conditions were found expanded, while genes involved in anoxic adaptation and phosphonate utilization are located on the megaplasmid, suggesting its indispensable role in environmental adaptation. Distinct gene expression patterns were observed during the light‐intensity‐regulated transition from hormogonia to vegetative filaments, specifically, genes encoding proteins involved in photosynthetic light reaction, carbon fixation, nitrogen metabolism and heterocyst differentiation were significantly upregulated, whereas genes related to cell motility were down‐regulated. Our results provide genomic and transcriptomic insights into the adaptation of a filamentous nitrogen‐fixing cyanobacterium to the highly dynamic paddy‐field habitat, suggesting N. sphaeroides as an excellent system to understand the transition from aquatic to terrestrial habitats and to support sustainable rice production.

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

Design, synthesis, and antidepressant/anticonvulsant activities of 3H-benzo[f]chromen chalcone derivatives - Qiu-Wan Tan; Li-Ya He; Zhi-Wen He; Wei-Hua Liu; Shan-Shan Zhang; Lin Lin; Hong-Li Yang; Li-Ping Guan (Medicinal Chemistry Research, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Dydrogesterone Affects the Transcription of Genes in Innate Immune and Coagulation Cascade in Zebrafish Embryos - Wen-Jun Shi; Yan‑Qiu Liang; Jian‑Liang Zhao; Li‑Xin Hu; Guo-Yong Huang; Guang-Guo Ying (Bulletin of Environmental Contamination and Toxicology, 2021)

High-Level Expression and Purification of Melittin in Escherichia coli Using SUMO Fusion Partner - Qiu-chi Chen; Lei Liu; Tian-Yi Yu; Lu Tang; Mo-li Yin; Wen-he Zhu; Xiu-yun Jiang; Hui-yan Wang (International Journal of Peptide Research and Therapeutics, 2021)

Paeonol ameliorates CFA-induced inflammatory pain by inhibiting HMGB1/TLR4/NF-κB p65 pathway - Chen Qiu; Liu-Di Yang; Wen Yu; Dan-Dan Tian; Mei-Rong Gao; Wen-Ju Wang; Xu-Bo Li; Yu-Mei Wu; Min Wang (Metabolic Brain Disease, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Connexin 36 Mediates Orofacial Pain Hypersensitivity Through GluK2 and TRPA1 - Qian Li; Tian-Le Ma; You-Qi Qiu; Wen-Qiang Cui; Teng Chen; Wen-Wen Zhang; Jing Wang; Qi-Liang Mao-Ying; Wen-Li Mi; Yan-Qing Wang; Yu-Xia Chu (Neuroscience Bulletin, 2020)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Clinical characteristics and plasma antibody titer of patients with COVID-19 in Zhejiang, China - Wei-ling Xiang; Jing-jing Cheng; Lian-peng Wu; Bing-yu Chen; Wen-xin Li; Dan-ying Qiu; Wei Zhang; Fei-hang Ge; Dong Chen; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2020)

AMPK-SIRT1-PGC1α Signal Pathway Influences the Cognitive Function of Aged Rats in Sevoflurane-Induced Anesthesia - Xiao-Yu Yang; Qiu-Jun Li; Wen-Chao Zhang; Shao-Qiang Zheng; Zhi-Jun Qu; Yang Xi; Geng Wang (Journal of Molecular Neuroscience, 2020)

A near-infrared spectroscopy-based end-point determination method for the blending process of Dahuang soda tablets - Si-jun Wu; Ping Qiu; Pian Li; Zheng Li; Wen-long Li (Journal of Zhejiang University-SCIENCE B, 2020)

Single-nucleotide polymorphisms influence the promoter activities of systemic lupus erythematosus-associated genes - Jinjun Qiu; Xiaoming Qin; Jinli Wen; Li Wu; Lei Kong; Yangxi Ou; Shucai Yang (Biotechnology Letters, 2020)

Identification of pleiotropic genes between risk factors of stroke by multivariate metaCCA analysis - Zun Wang; Jonathan Greenbaum; Chuan Qiu; Kelvin Li; Qian Wang; Si-Yuan Tang; Hong-Wen Deng (Molecular Genetics and Genomics, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

A new epicatechin glucopyranoside derivative from Styrax suberifolius - Bing-Lei Liu; Xin Hu; Hua-Liang He; Lin Qiu; You-Zhi Li; Wen-Bing Ding (Natural Product Research, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Identification of novel functional CpG-SNPs associated with type 2 diabetes and coronary artery disease - Zun Wang; Chuan Qiu; Xu Lin; Lan-Juan Zhao; Yong Liu; Xinrui Wu; Qian Wang; Wei Liu; Kelvin Li; Hong-Wen Deng; Si-Yuan Tang; Hui Shen (Molecular Genetics and Genomics, 2020)

Genome-wide association study of soybean seed germination under drought stress - Zhangxiong Liu; Huihui Li; Zuowang Gou; Yanjun Zhang; Xingrong Wang; Honglei Ren; Zixiang Wen; Beom-Kyu Kang; Yinghui Li; Lili Yu; Huawei Gao; Dechun Wang; et al. (Molecular Genetics and Genomics, 2020)

Comparative study of vermicomposting of garden waste and cow dung using Eisenia fetida - Yingkai Li; Xiaolei Yang; Wen Gao; Jiangping Qiu; Yinsheng Li (Environmental Science and Pollution Research, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Genomic characterization of a novel astrovirus identified in Amur tigers from a zoo in China - Hui-Hui Zhang; Qi-Guan Qiu; Shu-Jing Liu; Wen-Qin Hu; Jie-Yu Li; Tian-Ning Liu; You-Song Peng; Xing-Yi Ge; Chao-Ting Xiao (Archives of Virology, 2019)

Pseudomonas sp. UW4 acdS gene promotes primordium initiation and fruiting body development of Agaricus bisporus - Chaohui Zhang; Guang Zhang; Yamei Wen; Tao Li; Yuqian Gao; Fanmei Meng; Liyou Qiu; Yuncan Ai (World Journal of Microbiology and Biotechnology, 2019)

Association between occupational exposure to trichloroethylene and serum levels of microRNAs: a cross-sectional molecular epidemiology study in China - Kyoung-Mu Lee; Bryan A. Bassig; Luoping Zhang; Roel C. Vermeulen; Wei Hu; Jason Y. Y. Wong; Chuangyi Qiu; Cuiju Wen; Yongshun Huang; Mark P. Purdue; Bu-Tian Ji; Laiyu Li; et al. (International Archives of Occupational and Environmental Health, 2019)

Regulation of osteoblast behaviors via cross-talk between Hippo/YAP and MAPK signaling pathway under fluoride exposure - Wen-qing Zhu; Ying-juan Yu; Li-na Xu; Pan-pan Ming; Shui-yi Shao; Jing Qiu (Journal of Molecular Medicine, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Orange and red carotenoid proteins are involved in the adaptation of the terrestrial cyanobacterium Nostoc flagelliforme to desiccation - Yi-Wen Yang; Yan-Chao Yin; Zheng-Ke Li; Da Huang; Jin-Long Shang; Min Chen; Bao-Sheng Qiu (Photosynthesis Research, 2019)

Geochemistry, zircon U–Pb geochronology and Hf isotopes of Jurassic-Cretaceous granites in the Tengchong terrane, SW China: implications for the Mesozoic tectono-magmatic evolution of the Eastern Tethyan Tectonic Domain - Hua-Wen Cao; Yun-Hui Zhang; Li Tang; Steven P. Hollis; Shou-Ting Zhang; Qiu-Ming Pei; Chang Yang; Xiao-Shuan Zhu (International Geology Review, 2019)

Antibacterial activity and mechanism of ThDP analogs against rice brown stripe pathogen Acidovorax avenae subsp. avenae RS-1 - Xiao Xuan Wang; Hang Ying Qi; Jie Chen; Ying Zi Yang; Wen Qiu; Wei Wang; Peng Zou; Bin Li; Yan Li Wang; Hong Wu He; Guo Chang Sun (Journal of Plant Pathology, 2019)

Genomic and transcriptomic insights into the survival of the subaerial cyanobacterium Nostoc flagelliforme in arid and exposed habitats - Jin‐Long Shang; Min Chen; Shengwei Hou; Tao Li; Yi‐Wen Yang; Qi Li; Hai‐Bo Jiang; Guo‐Zheng Dai; Zhong‐Chun Zhang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2019)
Summary The cyanobacterium Nostoc flagelliforme is an extremophile that thrives under extraordinary desiccation and ultraviolet (UV) radiation conditions. To investigate its survival strategies, we performed whole‐genome sequencing of N. flagelliforme CCNUN1 and transcriptional profiling of its field populations upon rehydration in BG11 medium. The genome of N. flagelliforme is 10.23 Mb in size and contains 10 825 predicted protein‐encoding genes, making it one of the largest complete genomes of cyanobacteria reported to date. Comparative genomics analysis among 20 cyanobacterial strains revealed that genes related to DNA replication, recombination and repair had disproportionately high contributions to the genome expansion. The ability of N. flagelliforme to thrive under extreme abiotic stresses is supported by the acquisition of genes involved in the protection of photosynthetic apparatus, the formation of monounsaturated fatty acids, responses to UV radiation, and a peculiar role of ornithine metabolism. Transcriptome analysis revealed a distinct acclimation strategy to rehydration, including the strong constitutive expression of genes encoding photosystem I assembly factors and the involvement of post‐transcriptional control mechanisms of photosynthetic resuscitation. Our results provide insights into the adaptive mechanisms of subaerial cyanobacteria in their harsh habitats and have important implications to understand the evolutionary transition of cyanobacteria from aquatic environments to terrestrial ecosystems.

Plastic-film mulch and fertilization rate affect the fate of urea-15N in maize production - Qiu-Jin Ma; Xiao Gang Li; Wen-Yuan Song; Bin Jia; Qian Zhang; Limei Lin; Feng-Min Li (Nutrient Cycling in Agroecosystems, 2018)

Modelling of turbulent dispersion for numerical simulation of wind-driven rain on bridges - Man Liu; Sheng Hong Huang; Bo Wen Yan; Qiu Sheng Li (Environmental Fluid Mechanics, 2018)

Bioaccumulation and Cycling of Polycyclic Aromatic Hydrocarbons (PAHs) in Typical Mangrove Wetlands of Hainan Island, South China - Yao-Wen Qiu; Han-Lin Qiu; Jun Li; Gan Zhang (Archives of Environmental Contamination and Toxicology, 2018)

Response of host–bacterial colonization in shrimp to developmental stage, environment and disease - Jinbo Xiong; Wenfang Dai; Qiongfen Qiu; Jinyong Zhu; Wen Yang; Chenghua Li (Molecular Ecology, 2018)
The host‐associated microbiota is increasingly recognized to facilitate host fitness, but the understanding of the underlying ecological processes that govern the host–bacterial colonization over development and, particularly, under disease remains scarce. Here, we tracked the gut microbiota of shrimp over developmental stages and in response to disease. The stage‐specific gut microbiotas contributed parallel changes to the predicted functions, while shrimp disease decoupled this intimate association. After ruling out the age‐discriminatory taxa, we identified key features indicative of shrimp health status. Structural equation modelling revealed that variations in rearing water led to significant changes in bacterioplankton communities, which subsequently affected the shrimp gut microbiota. However, shrimp gut microbiotas are not directly mirrored by the changes in rearing bacterioplankton communities. A neutral model analysis showed that the stochastic processes that govern gut microbiota tended to become more important as healthy shrimp aged, with 37.5% stochasticity in larvae linearly increasing to 60.4% in adults. However, this defined trend was skewed when disease occurred. This departure was attributed to the uncontrolled growth of two candidate pathogens (over‐represented taxa). The co‐occurrence patterns provided novel clues on how the gut commensals interact with candidate pathogens in sustaining shrimp health. Collectively, these findings offer updated insight into the ecological processes that govern the host–bacterial colonization in shrimp and provide a pathological understanding of polymicrobial infections.

IcmF and DotU are required for the virulence of Acidovorax oryzae strain RS-1 - Bin Li; Xiaoxuan Wang; Jie Chen; He Liu; Khattak Arif Ali; Yanli Wang; Wen Qiu; Guochang Sun (Archives of Microbiology, 2018)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

Complete plastid genome of Larix potaninii var. macrocarpa, an endangered conifer endemic to China - Dai-Yu Qiu; Jiao Yang; Li Feng; Ding-Wen Ni; Cai-Xia Huang; Zhong-Hu Li (Conservation Genetics Resources, 2018)

Brittleness characteristics of tight oil siltstones - Wen-Hui Tan; Jing Ba; Meng-Qiu Guo; Hui Li; Lin Zhang; Ting Yu; Hao Chen (Applied Geophysics, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Efficient and Product-Controlled Depolymerization of Lignin Oriented by Raney Ni Cooperated with Cs x H3 − x PW12O40 - Xiao-Jun Shen; Jia-Long Wen; Pan-Li Huang; Kai Zheng; Shuang-Fei Wang; Qiu-Yun Liu; Adam Charlton; Run-Cang Sun (BioEnergy Research, 2017)

Combined Effects of Temperature and the Microcystin MC-LR on the Feeding Behavior of the Rotifer Brachionus calyciflorus - Xian-Ling Xiang; Ying-Ying Chen; Qiu-Lei Xu; Ling-Yun Zhu; Xin-Li Wen; Yi-Long Xi (Bulletin of Environmental Contamination and Toxicology, 2017)

Aquatic animals promote antibiotic resistance gene dissemination in water via conjugation: Role of different regions within the zebra fish intestinal tract, and impact on fish intestinal microbiota - Jialun Fu; Dong Yang; Min Jin; Weili Liu; Xin Zhao; Chenyu Li; Tianyu Zhao; Jingfeng Wang; Zhixian Gao; Zhiqiang Shen; Zhigang Qiu; Jun‐Wen Li (Molecular Ecology, 2017)
The aqueous environment is one of many reservoirs of antibiotic resistance genes ( ARG s). Fish, as important aquatic animals which possess ideal intestinal niches for bacteria to grow and multiply, may ingest antibiotic resistance bacteria from aqueous environment. The fish gut would be a suitable environment for conjugal gene transfer including those encoding antibiotic resistance. However, little is known in relation to the impact of ingested ARG s or antibiotic resistance bacteria ( ARB ) on gut microbiota. Here, we applied the cultivation method, qPCR , nuclear molecular genetic marker and 16S rDNA amplicon sequencing technologies to develop a plasmid‐mediated ARG transfer model of zebrafish. Furthermore, we aimed to investigate the dissemination of ARG s in microbial communities of zebrafish guts after donors carrying self‐transferring plasmids that encode ARG s were introduced in aquaria. On average, 15% of faecal bacteria obtained ARG s through RP 4‐mediated conjugal transfer. The hindgut was the most important intestinal region supporting ARG dissemination, with concentrations of donor and transconjugant cells almost 25 times higher than those of other intestinal segments. Furthermore, in the hindgut where conjugal transfer occurred most actively, there was remarkable upregulation of the mRNA expression of the RP 4 plasmid regulatory genes, trbBp and trfAp . Exogenous bacteria seem to alter bacterial communities by increasing Escherichia and Bacteroides species, while decreasing Aeromonas compared with control groups. We identified the composition of transconjugants and abundance of both cultivable and uncultivable bacteria (the latter accounted for 90.4%–97.2% of total transconjugants). Our study suggests that aquatic animal guts contribute to the spread of ARG s in water environments.

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Transcriptional and Biochemical Alterations in Zebrafish Eleuthero-Embryos (Danio rerio) After Exposure to Synthetic Progestogen Dydrogesterone - Wen-Jun Shi; Guang-Guo Ying; Guo-Yong Huang; Yan-Qiu Liang; Li-Xin Hu; Jian-Liang Zhao; Jin-Na Zhang (Bulletin of Environmental Contamination and Toxicology, 2017)

Molecular adaptation in the world's deepest‐living animal: Insights from transcriptome sequencing of the hadal amphipod Hirondellea gigas - Yi Lan; Jin Sun; Renmao Tian; Douglas H. Bartlett; Runsheng Li; Yue Him Wong; Weipeng Zhang; Jian‐Wen Qiu; Ting Xu; Li‐Sheng He; Harry G. Tabata; Pei‐Yuan Qian (Molecular Ecology, 2017)
The Challenger Deep in the Mariana Trench is the deepest point in the oceans of our planet. Understanding how animals adapt to this harsh environment characterized by high hydrostatic pressure, food limitation, dark and cold is of great scientific interest. Of the animals dwelling in the Challenger Deep, amphipods have been captured using baited traps. In this study, we sequenced the transcriptome of the amphipod Hirondellea gigas collected at a depth of 10,929 m from the East Pond of the Challenger Deep. Assembly of these sequences resulted in 133,041 contigs and 22,046 translated proteins. Functional annotation of these contigs was made using the go and kegg databases. Comparison of these translated proteins with those of four shallow‐water amphipods revealed 10,731 gene families, of which 5659 were single‐copy orthologs. Base substitution analysis on these single‐copy orthologs showed that 62 genes are positively selected in H. gigas , including genes related to β‐alanine biosynthesis, energy metabolism and genetic information processing. For multiple‐copy orthologous genes, gene family expansion analysis revealed that cold‐inducible proteins (i.e., transcription factors II A and transcription elongation factor 1) as well as zinc finger domains are expanded in H. gigas . Overall, our results indicate that genetic adaptation to the hadal environment by H. gigas may be mediated by both gene family expansion and amino acid substitutions of specific proteins.

Morphologies of eumelanins from the ink of six cephalopods species measured by atomic force microscopy - Yulin Sun; Li Tian; Jing Wen; Juan Zhao; Wei Zhang; Chunyao Xie; Meiqing Zhou; Xiaoying Qiu; Daohai Chen (Journal of Ocean University of China, 2017)

Two new dammarane-type triterpenoid saponins from ginseng medicinal fungal substance - Wei Xu; Jin-hui Zhang; Xin Liu; Ai-ling Jia; Xiao-li Liu; Xin-wen Wang; Zhi-dong Qiu (Natural Product Research, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Distinct Defects in Spine Formation or Pruning in Two Gene Duplication Mouse Models of Autism - Miao Wang; Huiping Li; Toru Takumi; Zilong Qiu; Xiu Xu; Xiang Yu; Wen-Jie Bian (Neuroscience Bulletin, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Identification of an iron permease, cFTR1, in cyanobacteria involved in the iron reduction/re‐oxidation uptake pathway - Ning Xu; Guo‐Wei Qiu; Wen‐Jing Lou; Zheng‐Ke Li; Hai‐Bo Jiang; Neil M. Price; Bao‐Sheng Qiu (Environmental Microbiology, 2016)
Summary Cyanobacteria are globally important primary producers and abundant in many iron‐limited aquatic environments. The ways in which they take up iron are largely unknown, but reduction of Fe 3+ is an important step in the process. Here we report a special iron permease in Synechocystis , cFTR1, that is required for Fe 3+ uptake following Fe 2+ re‐oxidation. The expression of cFTR1 is induced by iron starvation, and a mutant lacking the gene is abnormally sensitive to iron starvation. The cFTR1 protein localizes to the plasma membrane and contains the iron‐binding motif “REXXE”. Point‐directed mutagenesis of the REXXE motif results in a sensitivity to Fe‐deficiency. Measurements of iron ( 55 Fe) uptake rate show that cFTR1 takes up Fe 3+ rather than Fe 2+ . The function of cFTR1 in Synechocystis could be genetically complemented by the iron permease, Ftr1p, of Saccharomyces cerevisiae , that is known to transport Fe 3+ produced by the oxidation of Fe 2+ via a multicopper oxidase. Unlike yeast Ftr1p, cyanobacterial cFTR1 probably obtains Fe 3+ primarily from the oxidation of Fe 2+ by oxygen. Growth assays show that the cFTR1 is required during oxygenic, photoautotrophic growth but not when oxygen production is inhibited during photoheterotrophic growth. In cyanobacteria, iron reduction/re‐oxidation uptake pathway may represent their adaptation to oxygenated environments.

Influence of low protein diets on gene expression of digestive enzymes and hormone secretion in the gastrointestinal tract of young weaned piglets - Zhi-mei Tian; Xian-yong Ma; Xue-fen Yang; Qiu-li Fan; Yun-xia Xiong; Yue-qin Qiu; Li Wang; Xiao-lu Wen; Zong-yong Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Early detection of white mold caused by Sclerotinia sclerotiorum in potato fields using real-time PCR - Mohammad Reza Ojaghian; Jing-Ze Zhang; Fan Zhang; Wen Qiu; Xiao-Lin Li; Guan-Lin Xie; Shui-Jin Zhu (Mycological Progress, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

High throughput transformation of a Sorghum cDNA library for rice improvement - Kezhou Qin; Ping Qiu; Jianyu Wen; Yingguo Zhu; Nengwu Li; Shaoqing Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Transgenic NfFeSOD Sedum alfredii plants exhibited profound growth impairments and better relative tolerance to long-term abiotic stresses - Xiang Gao; Wen-Li Ai; Huan Gong; Li-Juan Cui; Bo-Xia Chen; Hong-Yi Luo; Zhong-Chun Zhang; Bao-Sheng Qiu (Plant Biotechnology Reports, 2016)

Quantitative phosphoproteomic analysis of early seed development in rice (Oryza sativa L.) - Jiehua Qiu; Yuxuan Hou; Xiaohong Tong; Yifeng Wang; Haiyan Lin; Qing Liu; Wen Zhang; Zhiyong Li; Babi R. Nallamilli; Jian Zhang (Plant Molecular Biology, 2016)

Differential distribution patterns of ammonia-oxidizing archaea and bacteria in acidic soils of Nanling National Nature Reserve forests in subtropical China - Xian-Hua Gan; Fang-Qiu Zhang; Ji-Dong Gu; Yue-Dong Guo; Zhao-Qing Li; Wei-Qiang Zhang; Xiu-Yu Xu; Yi Zhou; Xiao-Ying Wen; Guo-Guang Xie; Yong-Feng Wang (Antonie van Leeuwenhoek, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Soy 14-3-3 protein SGF14c, a new regulator of tolerance to salt–alkali stress - Youwen Qiu; Hongtao Wen; Jingxia Ao; Minghui Zhang; Fenglan Li (Plant Biotechnology Reports, 2015)

Enterobacter tabaci sp. nov., a novel member of the genus Enterobacter isolated from a tobacco stem - Yan-Qing Duan; Xing-Kui Zhou; Li Di-Yan; Qing-Qing Li; Li-Zhi Dang; Yong-Guang Zhang; Li-Hong Qiu; Salam Nimaichand; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Impacts of the Wenchuan earthquake on tree mortality and biomass carbon stock - Shuai Qiu; Ming Xu; Yunpu Zheng; Renqiang Li; Michelle Hang Gi Wong; Liyun Zhang; Lixiang Liu; Changhong Lai; Wen Zhang (Natural Hazards, 2015)

Inducible and constitutive expression of an elicitor gene Hrip1 from Alternaria tenuissima enhances stress tolerance in Arabidopsis - Xue-Cong Peng; De-Wen Qiu; Hong-Mei Zeng; Li-Hua Guo; Xiu-Fen Yang; Zheng Liu (Transgenic Research, 2015)

Geochronology and geochemistry of Grenville-aged (1063 ± 16 Ma) metabasalts in the Shennongjia district, Yangtze block: implications for tectonic evolution of the South China Craton - Xiao-Fei Qiu; Hong-Mei Yang; Shan-Song Lu; Wen-Li Ling; Li-Guo Zhang; Juan-Juan Tan; Zhi-Xian Wang (International Geology Review, 2015)

Polymorphic microsatellite markers in the long-spined sea urchin Diadema setosum - Mingling Wang; Zhe Li; Monthon Ganmanee; James Y. Xie; Juan Diego Urriago; Jian-Wen Qiu (Conservation Genetics Resources, 2014)

Association between serum vitamin D and severity of liver fibrosis in chronic hepatitis C patients: a systematic meta-analysis - Yue-qiu Luo; Xiao-xing Wu; Zong-xin Ling; Yi-wen Cheng; Li Yuan; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

A Short Peptide in Rice Glutelin Directs Trafficking of Protein into the Protein Storage Vacuoles of the Endosperm Cells - Wen Li; Tingting Xie; Qinchuan Qiu; Tingting Ning; Daichang Yang (Plant Molecular Biology Reporter, 2013)

Full-length sequence analysis of hepatitis E virus isolates: showing potential determinants of virus genotype and identity - Dong Yang; Mei Jiang; Min Jin; Zhigang Qiu; Weihong Cui; Zhiqiang Shen; Bo Li; Lianfeng Gong; Zhaoli Chen; Xinwei Wang; Jun-Wen Li (Virus Genes, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Identifying scale-location specific control on vegetation distribution in mountain-hill region - Bing-wen Qiu; Can-ying Zeng; Zheng-hong Tang; Wei-jiao Li; Aaron Hirsh (Journal of Mountain Science, 2013)
The scale-location specific control on vegetation distribution was investigated through continuous wavelet transforms approaches in subtropical mountain-hill region, Fujian, China. The Normalized Difference Vegetation Index (NDVI) was calculated as an indicator of vegetation greenness using Chinese Environmental Disaster Reduction Satellite images along latitudinal and longitudinal transects. Four scales of variations were identified from the local wavelet spectrum of NDVI, with much stronger wavelet variances observed at larger scales. The characteristic scale of vegetation distribution within mountainous and hilly regions in Southeast China was around 20 km. Significantly strong wavelet coherency was generally examined in regions with very diverse topography, typically characterized as small mountains and hills fractured by rivers and residents. The continuous wavelet based approaches provided valuable insight on the hierarchical structure and its corresponding characteristic scales of ecosystems, which might be applied in defining proper levels in multilevel models and optimal bandwidths in Geographically Weighted Regression.

Synthesis, molecular modeling, and biological evaluation of 1,2,4-triazole derivatives containing pyridine as potential anti-tumor agents - Yan-Bin Zhang; Wen Liu; Yu-Shun Yang; Xiao-Liang Wang; Hai-Liang Zhu; Li-Fei Bai; Xiao-Yang Qiu (Medicinal Chemistry Research, 2013)

Efficient and stable rescue of classical swine fever virus from cloned cDNA using an RNA polymerase II system - Chao Li; Junhua Huang; Yongfeng Li; Fan He; Dan Li; Yuan Sun; Wen Han; Su Li; Hua-Ji Qiu (Archives of Virology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Acute and Chronic Toxicity of Buprofezin on Daphnia Magna and the Recovery Evaluation - Yong Liu; Suzhen Qi; Wen Zhang; Xuefeng Li; Lihong Qiu; Chengju Wang (Bulletin of Environmental Contamination and Toxicology, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Molecular characterization and expression analysis on two isogenes encoding 3-deoxy-d-arabino-heptulosonate 7-phosphate synthase in grapes - Zhen-Zhen Zhang; Xiao-Xi Li; Bao-Qing Zhu; Ya-Qin Wen; Chang-Qing Duan; Qiu-Hong Pan (Molecular Biology Reports, 2011)

Comparative studies on tolerance of Medicago truncatula and Medicago falcata to freezing - Li-Li Zhang; Min-Gui Zhao; Qiu-Ying Tian; Wen-Hao Zhang (Planta, 2011)

Polycyclic aromatic hydrocarbons in surface sediments of the Jialu River - Jie Fu; Sheng Sheng; Teng Wen; Zhi-Ming Zhang; Qing Wang; Qiu-Xiang Hu; Qing-Shan Li; Shu-Qing An; Hai-Liang Zhu (Ecotoxicology, 2011)

Lack of association between methylenetetrahydrofolate reductase gene A1298C polymorphism and breast cancer susceptibility - Li-Xin Qiu; Jian Zhang; Wen-Hua Li; Qun-Ling Zhang; Hui Yu; Bi-Yun Wang; Lei-Ping Wang; Jia-Lei Wang; Hui-Jie Wang; Xiao-Jian Liu; Zhi-Guo Luo; Xiang-Hua Wu (Molecular Biology Reports, 2011)

BRAF V600E mutation and resistance to anti-EGFR monoclonal antibodies in patients with metastatic colorectal cancer: a meta-analysis - Chen Mao; Ru-Yan Liao; Li-Xin Qiu; Xi-Wen Wang; Hong Ding; Qing Chen (Molecular Biology Reports, 2011)

Elevated sICAM-1 levels in patients with hemorrhagic fever with renal syndrome caused by Hantaan virus - Qunying Han; Lei Zhang; Zhengwen Liu; Wen Kang; Sai Lou; Jianming Qiu; Zhu Li; Guoyu Zhang; Yawen Wang; Man Li; Na Li (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Millennial-centennial scales climate changes of Holocene indicated by magnetic susceptibility of high-resolution section in Salawusu River valley, China - Yingxia Lu; Baosheng Li; Xiaohao Wen; Shifan Qiu; Fengnian Wang; Dongfeng Niu; Zhiwen Li (Chinese Geographical Science, 2010)

UNC-64 and RIC-4, the plasma membrane-associated SNAREs syntaxin and SNAP-25, regulate fat storage in nematode Caenorhabditis elegans - Qiu-Li Wu; Qi Rui; Ke-Wen He; Lu-Lu Shen; Da-Yong Wang (Neuroscience Bulletin, 2010)

Association of melamine exposure with urinary stone and oxidative DNA damage in infants - Yuebin Ke; Xiaobei Duan; Feiqiu Wen; Xinyun Xu; Gonghua Tao; Li Zhou; Renli Zhang; Baoming Qiu (Archives of Toxicology, 2010)

GmRFP1 encodes a previously unknown RING-type E3 ubiquitin ligase in Soybean (Glycine max) - Qiu-Li Du; Wen-Zhuo Cui; Chun-Hong Zhang; De-Yue Yu (Molecular Biology Reports, 2010)

An improved process for cell disruption and astaxanthin extraction from Phaffia rhodozyma - An-Feng Xiao; Hui Ni; Hui-Nong Cai; Li-Jun Li; Wen-Jin Su; Qiu-Ming Yang (World Journal of Microbiology and Biotechnology, 2009)

Oxidative Damage of the Extracts of Condensate, Particulate and Semivolatile Organic Compounds from Gasoline Engine Exhausts on Testicles of Rats - Wangjun Che; Hong Qiu; Guiming Liu; Yun Ran; Hao Zhang; Li Zhang; Weihua Wen (Bulletin of Environmental Contamination and Toxicology, 2009)

Isolation and characterization of microsatellite loci in Ostryopsis davidiana (Betulaceae) - Qiang Qiu; Bin Tian; Hong-Yan Wen; Gui-Li Wu; Yu-Jin Wang (Conservation Genetics, 2009)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

A Novel Camptothecin Derivative Incorporated in Nano-Carrier Induced Distinguished Improvement in Solubility, Stability and Anti-tumor Activity Both In Vitro and In Vivo - Min Han; Cai-Xia He; Qiu-Li Fang; Xiao-Chun Yang; Yuan-Yuan Diao; Dong-Hang Xu; Qiao-Jun He; Yong-Zhou Hu; Wen-Quan Liang; Bo Yang; Jian-Qing Gao (Pharmaceutical Research, 2009)

Mutation characteristics of the PAH gene in four nationality groups in Xinjiang of China - Wu-Zhong Yu; Dong-Hui Qiu; Fang Song; Li Liu; Shao-Ming Liu; Yu-Wei Jin; Yan-Ling Zhang; Hong-Yun Zou; Jiang He; Quan Lei; Xing-Wen Liu (Journal of Genetics, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Cold events of Holocene indicated by primary elements distribution of the high-resolution sand dunes in the Salawusu River Valley - Dongfeng Niu; Baosheng Li; Shuhuan Du; Xiaohao Wen; Shifan Qiu; Xianjiao Ou; Yi Yang (Journal of Geographical Sciences, 2008)

Long-term aerobic exercise protects the heart against ischemia/reperfusion injury via PI3 kinase-dependent and Akt-mediated mechanism - Kun-Ru Zhang; Hai-Tao Liu; Hai-Feng Zhang; Quan-Jiang Zhang; Qiu-Xia Li; Qiu-Jun Yu; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2007)

Physical mapping and identification of a candidate for the leaf rust resistance gene Lr1 of wheat - Ji-Wen Qiu; Anita Christina Schürch; Nabila Yahiaoui; Ling-Li Dong; Hua-Jie Fan; Zhong-Juan Zhang; Beat Keller; Hong-Qing Ling (Theoretical and Applied Genetics, 2007)

Hypoxic postconditioning enhances the survival and inhibits apoptosis of cardiomyocytes following reoxygenation: role of peroxynitrite formation - Hai-Chang Wang; Hai-Feng Zhang; Wen-Yi Guo; Hui Su; Kun-Ru Zhang; Qiu-Xia Li; Wenli Yan; Xin L. Ma; Bernard L. Lopez; Theodore A. Christopher; Feng Gao (Apoptosis, 2006)

Cloning and localization of vip3A gene of Bacillus thuringiensis - Zeng Ling Wu; Wen Yi Guo; Jun Zhi Qiu; Tian Pei Huang; Xun Bo Li; Xiong Guan (Biotechnology Letters, 2004)